Quantifying the mitigation effect of natural landscapes during an extraordinary flood: the prominent role of the Otter Creek wetlands to middlebury, Vermont, USA, during Tropical Storm Irene - Lachapelle, Simon; Rousseau, Alain N.; Blanchette, Marianne; Foulon, Etienne; Savary, Stéphane (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2025)
Keywords: Infolettre; Infolettre_Avril_2025

Economic Exposure of Canadian Residential Properties to Flooding - Morin, Gabriel; Boudreault, Mathieu; Thistlethwaite, Jason; Bourdeau‐Brien, Michael; Chenette, Jacob; Henstra, Daniel; Raikes, Jonathan (Journal of Flood Risk Management, 2025)
ABSTRACT Flood risk management (FRM) involves planning proactively for flooding in high‐risk areas to reduce its impacts on people and property. A key challenge for governments pursuing FRM is to pinpoint assets that are highly economically exposed and vulnerable to flood hazards in order to prioritize them in policy and planning. This paper presents a novel flood risk assessment, making use of a dataset that identifies the location, dwelling type, property characteristics, and potential economic losses of Canadian residential properties. The findings reveal that the average annual costs are $1.4B, but most of the risks are concentrated in high‐risk areas. Data gaps are uncovered that justify replication through local validation studies. The results provide a novel evidence base for specific reforms in Canada's approach to FRM, with a focus on insurance that improves both implementation and effectiveness.
Keywords: Infolettre; Infolettre_Mars_2025

Limits of Blue and Green Infrastructures to Adapt Actual Urban Drainage Systems to the Impact of Climate Change - Benoit, Thomas; Martel, Jean-Luc; Bilodeau, Émilie; Brissette, François; Charron, Alain; Brulé, Dominic; Rivard, Gilles; Deslauriers, Simon (Journal of Irrigation and Drainage Engineering, 2025)
Keywords: Infolettre; Infolettre_Mars_2025

Meteorologically Related Factors Leading to the 2008, 2018, and 2019 Major Spring Floods in the Transboundary Saint John River (Wolastoq) Basin - Rickard, Lisa J.; Déry, Stephen J.; Stewart, Ronald E.; Thériault, Julie M. (Journal of Hydrometeorology, 2025)
Abstract The flood-prone Saint John River (SJR, Wolastoq), which lies within a drainage basin of 55 110 km 2 , flows a length of 673 km from its source in northern Maine, United States, to its mouth in southern New Brunswick, Canada. Major industries in the basin include forestry, agriculture, and hydroelectric power. During the 1991–2020 reference period, the SJR basin (SJRB) experienced major spring flood events in 2008, 2018, and 2019. As part of the Saint John River Experiment on Cold Season Storms, the objective of this research is to characterize and contrast these three major spring flood events. Given that the floods all occurred during spring, the hypothesis being tested is that rapid snowmelt alone is the dominant driver of flooding in the SJRB. There were commonalities and differences regarding the contributing factors of the three flood years. When averaged across the upper basin, they showed consistency in terms of positive winter and spring total precipitation anomalies, positive snow water equivalent anomalies, and steep increases in April cumulative runoff. Rain-on-snow events were a prominent feature of all three flood years. However, differences between flood years were also evident, including inconsistencies with respect to ice jams and high tides. Certain factors were present in only one or two of the three flood years, including positive total precipitation anomalies in spring, positive heavy liquid precipitation anomalies in spring, positive heavy solid precipitation anomalies in winter, and positive temperature anomalies in spring. The dominant factor contributing to peak water levels was rapid snowmelt.
Keywords: Infolettre; Infolettre_Mars_2025

Assessing hydrological erosion estimation using the Revised Universal Soil Loss Equation (RUSLE) model in Google Earth Engine: a case study of Medjerda River Catchment, Tunisia - Cherif, Mouna; Saidi, Salwa; Ezzine, Ahmed; Darragi, Fadila; Homayouni, Saeid (Euro-Mediterranean Journal for Environmental Integration, 2025)
Keywords: Infolettre; Infolettre_Mars_2025

Flooding: Contributing factors to residential flood damage in Canada - Deschamps, Bernard; Boudreault, Mathieu; Gachon, Philippe (International Journal of Disaster Risk Reduction, 2025)
Keywords: Gachon_Philippe; Infolettre; Infolettre_Avril_2025; Infolettre_Mars_2025

Nanoplastics in Water: Artificial Intelligence-Assisted 4D Physicochemical Characterization and Rapid In Situ Detection - Wang, Zi; Pal, Devendra; Pilechi, Abolghasem; Ariya, Parisa A. (Environmental Science & Technology, 2024)

Hybrid artificial intelligence-time series models for monthly streamflow modeling - Mehdizadeh, Saeid; Fathian, Farshad; Adamowski, Jan F. (Applied Soft Computing, 2019)

Comparative assessment of time series and artificial intelligence models to estimate monthly streamflow: A local and external data analysis approach - Mehdizadeh, Saeid; Fathian, Farshad; Safari, Mir Jafar Sadegh; Adamowski, Jan F. (Journal of Hydrology, 2019)

A global review on hydrological responses to forest change across multiple spatial scales: Importance of scale, climate, forest type and hydrological regime - Zhang, Mingfang; Liu, Ning; Harper, Richard; Li, Qiang; Liu, Kuan; Wei, Xiaohua; Ning, Dingyuan; Hou, Yiping; Liu, Shirong (Journal of Hydrology, 2017)
Keywords: Ouvrage_Collectif_Numéro1

Contributions of climate, elevated atmospheric CO2 concentration and land surface changes to variation in water use efficiency in Northwest China - Yang, Linshan; Feng, Qi; Wen, Xiaohu; Barzegar, Rahim; Adamowski, Jan F; Zhu, Meng; Yin, Zhenliang (CATENA, 2022)

Uncertainty of gridded precipitation and temperature reference datasets in climate change impact studies - Tarek, Mostafa; Brissette, François; Arsenault, Richard (Hydrology and Earth System Sciences, 2021)
Abstract. Climate change impact studies require a reference climatological dataset providing a baseline period to assess future changes and post-process climate model biases. High-resolution gridded precipitation and temperature datasets interpolated from weather stations are available in regions of high-density networks of weather stations, as is the case in most parts of Europe and the United States. In many of the world's regions, however, the low density of observational networks renders gauge-based datasets highly uncertain. Satellite, reanalysis and merged product datasets have been used to overcome this deficiency. However, it is not known how much uncertainty the choice of a reference dataset may bring to impact studies. To tackle this issue, this study compares nine precipitation and two temperature datasets over 1145 African catchments to evaluate the dataset uncertainty contribution to the results of climate change studies. These deterministic datasets all cover a common 30-year period needed to define the reference period climate. The precipitation datasets include two gauge-only products (GPCC and CPC Unified), two satellite products (CHIRPS and PERSIANN-CDR) corrected using ground-based observations, four reanalysis products (JRA55, NCEP-CFSR, ERA-I and ERA5) and one merged gauged, satellite and reanalysis product (MSWEP). The temperature datasets include one gauged-only (CPC Unified) product and one reanalysis (ERA5) product. All combinations of these precipitation and temperature datasets were used to assess changes in future streamflows. To assess dataset uncertainty against that of other sources of uncertainty, the climate change impact study used a top-down hydroclimatic modeling chain using 10 CMIP5 (fifth Coupled Model Intercomparison Project) general circulation models (GCMs) under RCP8.5 and two lumped hydrological models (HMETS and GR4J) to generate future streamflows over the 2071–2100 period. Variance decomposition was performed to compare how much the different uncertainty sources contribute to actual uncertainty. Results show that all precipitation and temperature datasets provide good streamflow simulations over the reference period, but four precipitation datasets outperformed the others for most catchments. They are, in order, MSWEP, CHIRPS, PERSIANN and ERA5. For the present study, the two-member ensemble of temperature datasets provided negligible levels of uncertainty. However, the ensemble of nine precipitation datasets provided uncertainty that was equal to or larger than that related to GCMs for most of the streamflow metrics and over most of the catchments. A selection of the four best-performing reference datasets (credibility ensemble) significantly reduced the uncertainty attributed to precipitation for most metrics but still remained the main source of uncertainty for some streamflow metrics. The choice of a reference dataset can therefore be critical to climate change impact studies as apparently small differences between datasets over a common reference period can propagate to generate large amounts of uncertainty in future climate streamflows.

Large-Scale Analysis of Global Gridded Precipitation and Temperature Datasets for Climate Change Impact Studies - Tarek, Mostafa; Brissette, François P.; Arsenault, Richard (Journal of Hydrometeorology, 2020)
Abstract Currently, there are a large number of diverse climate datasets in existence, which differ, sometimes greatly, in terms of their data sources, quality control schemes, estimation procedures, and spatial and temporal resolutions. Choosing an appropriate dataset for a given application is therefore not a simple task. This study compares nine global/near-global precipitation datasets and three global temperature datasets over 3138 North American catchments. The chosen datasets all meet the minimum requirement of having at least 30 years of available data, so they could all potentially be used as reference datasets for climate change impact studies. The precipitation datasets include two gauged-only products (GPCC and CPC-Unified), two satellite products corrected using ground-based observations (CHIRPS V2.0 and PERSIANN-CDR V1R1), four reanalysis products (NCEP CFSR, JRA55, ERA-Interim, and ERA5), and one merged product (MSWEP V1.2). The temperature datasets include one gauge-based (CPC-Unified) and two reanalysis (ERA-Interim and ERA5) products. High-resolution gauge-based gridded precipitation and temperature datasets were combined as the reference dataset for this intercomparison study. To assess dataset performance, all combinations were used as inputs to a lumped hydrological model. The results showed that all temperature datasets performed similarly, albeit with the CPC performance being systematically inferior to that of the other three. Significant differences in performance were, however, observed between the precipitation datasets. The MSWEP dataset performed best, followed by the gauge-based, reanalysis, and satellite datasets categories. Results also showed that gauge-based datasets should be preferred in regions with good weather network density, but CHIRPS and ERA5 would be good alternatives in data-sparse regions.

Climate Change and Land: an IPCC special report on climate change, desertification, land degradation, sustainable land management, food security, and greenhouse gas fluxes in terrestrial ecosystems - Shukla, P.; Skeg, J.; Buend́ıa, E.; Masson‐Delmotte, V.; Pörtner, H.; Roberts, D.; Zhai, P.; Slade, R.; Connors, S.; Diemen, S. V.; Ferrat, M.; Haughey, E.; et al. (2019)
The following errata have been identified and approved in accordance with the IPCC protocol for addressing possible errors in IPCC assessment reports, synthesis reports and methodology reports as adopted by the Panel at the Thirty-Third Session (Abu Dhabi, 10-13 May 2011) and amended at the Thirty-Seventh Session (Batumi 14-18 October 2013). Errata identified following the approval and acceptance of the Special Report on Climate Change and Land (SRCCL) and prior to publication have been corrected in the final copyedited and laid out draft of the report. Note that page and line numbers for the SPM are based on the numbering used in the revised final draft as distributed Governments st 2019; and line numbers for the underlying chapters are based on the numbering used in the final draft as distributed to Governments on 24 th June 2019.
Keywords: Ouvrage_Collectif_Numéro1

Adaptation to Climate Change: Risk Management - Simonovic, Slobodan P. (2017)
Adaptation to climate change is a challenge that is complex and involves increasing risk. Efforts to manage these risks involve many decision-makers, conflicting values, competing objectives and methodologies, multiple alternative options, uncertain outcomes, and debatable probabilities. Adaptation occurs at multiple levels in a complex decision environment and is generally evaluated as better–worse, not right–wrong, based on multiple criteria. Identifying the best adaptation response is difficult. Risk management techniques help to overcome these problems. Here, risk management is presented as a decision-making framework that assists in the selection of optimal strategies (according to various criteria) using a systems approach that has been well defined and generally accepted in public decision-making. In the context of adapting to climate change, the risk management process offers a framework for identifying, assessing, and prioritizing climate-related risks and developing appropriate adaptation responses. The theoretical discussion is illustrated with an example from Canada. It includes (a) the assessment of climate change-caused flood risk to the municipal infrastructure for the City of London, Ontario, Canada, and (b) analysis of adaptation options for management of the risk in one of the watersheds within the City of London – Dingman Creek.
MAG ID: 2531992390

Climate change and the nonlinear impact of precipitation anomalies on income inequality - Palagi, Elisa; Coronese, Matteo; Lamperti, Francesco; Roventini, Andrea (Proceedings of the National Academy of Sciences, 2022)
Climate anomalies, such as floods and droughts, as well as gradual temperature changes have been shown to adversely affect economies and societies. Although studies find that climate change might increase global inequality by widening disparities across countries, its effects on within-country income distribution have been little investigated, as has the role of rainfall anomalies. Here, we show that extreme levels of precipitation exacerbate within-country income inequality. The strength and direction of the effect depends on the agricultural intensity of an economy. In high-agricultural-intensity countries, climate anomalies that negatively impact the agricultural sector lower incomes at the bottom end of the distribution and generate greater income inequality. Our results indicate that a 1.5-SD increase in precipitation from average values has a 35-times-stronger impact on the bottom income shares for countries with high employment in agriculture compared to countries with low employment in the agricultural sector. Projections with modeled future precipitation and temperature reveal highly heterogeneous patterns on a global scale, with income inequality worsening in high-agricultural-intensity economies, particularly in Africa. Our findings suggest that rainfall anomalies and the degree of dependence on agriculture are crucial factors in assessing the negative impacts of climate change on the bottom of the income distribution.

The diffusion of climate change adaptation policy - Schoenefeld, Jonas J.; Schulze, Kai; Bruch, Nils (Wiley Interdisciplinary Reviews: Climate Change, 2022)
Adapting to some level of climate change has become unavoidable. However, there is surprisingly limited systematic knowledge about whether and how adaptation policies have diffused and could diffuse in the future. Most existing adaptation studies do not explicitly examine policy diffusion, which is a form of interdependent policy-making among jurisdictions at the same or across different levels of governance. To address this gap, we offer a new interpretation and assessment of the extensive adaptation policy literature through a policy diffusion perspective; we pay specific attention to diffusion drivers and barriers, motivations, mechanisms, outputs, and outcomes. We assess the extent to which four motivations and related mechanisms of policy diffusion—interests (linked with learning and competition), rights and duties (tied to coercion), ideology, and recognition (both connected with emulation)—are conceptually and empirically associated with adaptation. We also engage with adaptation policy characteristics, contextual conditions (e.g., problem severity) and different channels of adapation policy diffusion (e.g., transnational networks). We demonstrate that adaptation policy diffusion can be associated with different mechanisms, yet many of them remain remarkably understudied. So are the effects of adaptation policy diffusion in terms of changes in vulnerability and resilience. We thus identify manifold avenues for future research, and provide insights for practitioners who may hope to leverage diffusion mechanisms to enhance their adaptation efforts. This article is categorized under: Policy and Governance > Multilevel and Transnational Climate Change Governance Vulnerability and Adaptation to Climate Change > Institutions for Adaptation
MAG ID: 4221081341

A temporal downscaling approach for sub-daily gridded extreme rainfall intensity estimation under climate change - Requena, Ana I.; Nguyen, Truong-Huy; Burn, Donald H.; Coulibaly, Paulin; Nguyen, Van-Thanh-Van (Journal of Hydrology: Regional Studies, 2021)

Using the Mann–Kendall test and double mass curve method to explore stream flow changes in response to climate and human activities - Pirnia, Abdollah; Golshan, Mohammad; Darabi, Hamid; Adamowski, Jan; Rozbeh, Sajad (Journal of Water and Climate Change, 2019)
Abstract Analyzing intra-annual stream flow can reveal the main causes for runoff changes and the contributions of climate variability and human activities. For this purpose, the Mann–Kendall and cumulative rank difference (CRD) tests, and the double mass curve method, were applied to a time series of hydro-meteorological variables from 1971 to 2010 in the Tajan River basin in Iran. Results indicated that runoff changes in the wet and dry seasons after 1999 had significant respective decreasing and increasing trends, at the 0.01 confidence level, due to dam construction. In the pre-dam period (1991–1998), the results of the double mass curve method showed that climate variability and human activities contributed 57.76% and 42.24%, respectively, to the runoff decrease during the wet season. For the post-dam period (1999–2010), climate variability and anthropogenic activities contributed 24.68% and 75.32%, respectively, to the wet season runoff decrease of 116.55 mm. On the other hand, in the same period during the dry season, climate variability contributed −30.68% and human activities contributed 130.68% to the runoff increase of 41.45 mm. It is evident that runoff changes in both wet and dry seasons were mainly due to human activities associated with dam construction to meet water supply demands for agriculture.

Hydrological responses of a watershed to historical land use evolution and future land use scenarios under climate change conditions - Quilbé, R.; Rousseau, A. N.; Moquet, J.-S.; Savary, S.; Ricard, S.; Garbouj, M. S. (Hydrology and Earth System Sciences, 2008)
Watershed runoff is closely related to land use but this influence is difficult to quantify. This study focused on the Chaudière River watershed (Québec,...
Publisher: Copernicus Publications
Keywords: Ouvrage_Collectif_Numéro1; Rousseau_Alain

Beyond fear: The role of emotions in disaster risk reduction in the face of climate change - Lizarralde, Gonzalo; Lajoie, Steffen; Gould, Kevin; Araneda, Claudio; Cruz-Panesso, Ilian; Diaz, Julia Helena; Monsalve, Elsa; Burdiles, Roberto; Herazo, Benjamin; Páez, Holmes; Valladares, Arturo; Bornstein, Lisa; et al. (Emotion, Space and Society, 2025)
Keywords: Infolettre; Infolettre_Decembre_2024

A Novel Statistical Modeling Approach to Developing IDF Relations in the Context of Climate Change - Nguyen, Van-Thanh-Van; Nguyen, Truong-Huy (Journal of Water Management Modeling, 2022)
Extreme rainfall intensity–duration–frequency (IDF) relations have been commonly used for estimating the design storm for the design of various urban water infrastructures. In recent years, climate change has been recognized as having a profound impact on the hydrologic cycle. Hence, the derivation of IDF relations in the context of a changing climate has been recognized as one of the most challenging tasks in current engineering practice. The main challenge is how to establish the linkages between the climate projections given by climate models at the global or regional scales and the observed extreme rainfalls at a local site of interest. Therefore, our overall objective is to introduce a new statistical modeling approach to linking global or regional climate predictors to the observed daily and sub-daily rainfall extremes at a given location. Illustrative applications using climate simulations from 21 different global climate models and extreme rainfall data available from rain gauge networks located across Canada are presented to indicate the feasibility, accuracy, and robustness of the proposed modeling approach for assessing the climate change impact on IDF relations.
Keywords: Infolettre; Infolettre_Septembre_2022; Site_internet_RIISQ

Does climate change cause disasters? How citizens, academics, and leaders explain climate-related risk and disasters in Latin America and the Caribbean - Lizarralde, Gonzalo; Bornstein, Lisa; Robertson, Mélanie; Gould, Kevin; Herazo, Benjamín; Petter, Anne-Marie; Páez, Holmes; Díaz, Julia Helena; Olivera, Andrés; González, Gonzalo; López, Oswaldo; López, Adriana; et al. (International Journal of Disaster Risk Reduction, 2021)
Keywords: Lizarralde_Gonzalo

Climate Change and Rainfall Intensity–Duration–Frequency Curves: Overview of Science and Guidelines for Adaptation - Martel, Jean-Luc; Brissette, François P.; Lucas-Picher, Philippe; Troin, Magali; Arsenault, Richard (Journal of Hydrologic Engineering, 2021)

We said, they said: the politics of conceptual frameworks in disasters and climate change in Colombia and Latin America - Lizarralde, Gonzalo; Páez, Holmes; Lopez, Adriana; Lopez, Oswaldo; Bornstein, Lisa; Gould, Kevin; Herazo, Benjamin; Muñoz, Lissette (Disaster Prevention and Management: An International Journal, 2020)
Purpose Few people living in informal settlements in the Global South spontaneously claim that they are “resilient” or “adapting” to disaster risk or climate change. Surely, they often overcome multiple challenges, including natural hazards exacerbated by climate change. Yet their actions are increasingly examined through the framework of resilience, a notion developed in the North, and increasingly adopted in the South. To what extent eliminate’ do these initiatives correspond to the concepts that scholars and authorities place under the resilience framework? Design/methodology/approach Three longitudinal case studies in Yumbo, Salgar and San Andrés (Colombia) serve to investigate narratives of disaster risks and responses to them. Methods include narrative analysis from policy and project documents, presentations, five workshops, six focus groups and 24 interviews. Findings The discourse adopted by most international scholars and local authorities differs greatly from that used by citizens to explain risk and masks the politics involved in disaster reduction and the search for social justice. Besides, narratives of social change, aspirations and social status are increasingly masked in disaster risk explanations. Tensions are also concealed, including those regarding the winners and losers of interventions and the responsibilities for disaster risk reduction. Originality/value Our findings confirm previous results that have shown that the resilience framework contributes to “depoliticize” the analysis of risk and serves to mask and dilute the responsibility of political and economic elites in disaster risk creation. But they also show that resilience fails to explain the type of socioeconomic change that is required to reduce vulnerabilities in Latin America.
Keywords: Lizarralde_Gonzalo

Welfare in the 21st century: Increasing development, reducing inequality, the impact of climate change, and the cost of climate policies - Lomborg, Bjorn (Technological Forecasting and Social Change, 2020)

Power and politics in climate change adaptation efforts: Struggles over authority and recognition in the context of political instability - Nightingale, Andrea J. (Geoforum, 2017)

How children make sense of climate change: A descriptive qualitative study of eco-anxiety in parent-child dyads - Léger-Goodes, Terra; Malboeuf-Hurtubise, Catherine; Hurtubise, Karen; Simons, Kyra; Boucher, Amélie; Paradis, Pier-Olivier; Herba, Catherine M.; Camden, Chantal; Généreux, Mélissa (PLOS ONE, 2023)
The climate crisis not only has significant impacts on biodiversity and the physical health of humans, but its ramifications are also affecting people’s mental health. Eco-anxiety, or the emotions that emerge with the awareness of climate change and the apprehension of its detrimental effects, has been investigated in adults and adolescents, but much less attention has been given to the impacts on children’s mental health and well-being. Initial evidence confirms that youth are significantly concerned about climate change, but few studies have investigated the resulting emotional responses of children and the role of their parents in tempering these, especially using qualitative methodologies. The present study used a descriptive qualitative design with a convenience sample of parents and child dyads, assessed separately. Children’s ( n = 15, ages 8–12 years) experiences were explored using semi-structured interviews and their parents’ ( n = 12) perceptions were captured using a survey with closed and open-ended questions. A reflexive thematic analysis was used to analyze the interview data, and content analysis was used to investigate parent-child experiences. Three themes emerged from the thematic analysis: 1. children’s understanding of climate change, 2. their emotional reaction to climate change, and 3. their coping mechanisms to deal with these emotions. The comparative content analysis revealed that parents who were aware that their children had concerns about climate change, had children who used more adaptive coping mechanisms. The results of this qualitative study contribute to a better understanding of children’s emotional experience of the awareness of climate change in Canada and how they cope with these emotions. Furthermore, the results provide insight into the role parents might play in helping their children cope with their feelings.
Keywords: Généreux_Mélissa

Local agency, adaptation, and planning betwixt and between urban risks and climate change in Panorama, Colombia - Lajoie, Steffen (2024)
Cette thèse explore l'adaptation urbaine au changement climatique dans les quartiers informels du Sud Global. Ce sont des lieux de grands défis et de réponses innovantes. Le contexte mondial d’exclusion postcoloniale et capitaliste entraîne la vulnérabilité et le risque supplémentaire du changement climatique augmente ces aléas contextuels. Des chercheurs ont critiqué les réponses traditionnelles en matière de planification de l’adaptation, les jugeant trop prescriptives, technologiquement dépendantes et manquant les besoins locaux. L’adaptation communautaire peut être trop isolée et axée sur les besoins des individus et des élites face à la diversité des défis locaux. Ni l’un ni l’autre ne prennent en compte les dimensions politiques de la planification de l’adaptation. En réponse, les spécialistes critiques de l’adaptation urbaine ont appelé à une meilleure compréhension des expériences locales afin de comprendre comment les gens priorisent, négocient et réagissent à une multiplicité de risques. En réponse à ces appels, ce projet cherche à mieux comprendre comment les gens perçoivent et répondent à ces défis à travers une étude de cas unique et exploratoire. Grâce à l’étude de cas qualitative dans le quartier de Panorama, situé dans la municipalité de Yumbo, en banlieue de Cali en Colombie, le projet cherche à comprendre comment l'identité et le pouvoir influencent l'accès aux ressources et aux institutions nécessaires pour s'adapter. Le projet se concentre sur deux sites de Panorama : un comité local d'aménagement soucieux de la sécurité foncière et une fondation écologique travaillant sur la conservation des espaces verts. Les résultats mettent en évidence des règles du jeu inégales où les habitants les plus vulnérables empruntent des voies parfois illégales pour accéder à la terre et au logement. Plus les résidents sont établis, plus ils bénéficient d'avantages et d'expérience pour jouer le système. Les dirigeants et les experts travaillent dur pour négocier entre les formalités. Cependant, l’absence d’un processus de planification transparent laisse divers intérêts se disputer les ressources, ce qui conduit parfois à des conflits et met fin à la créativité. Les résultats de la recherche suggèrent que la planification de l’adaptation urbaine dans les contextes informels des pays du Sud doit continuer à s’appuyer sur des recherches et des pratiques qui tiennent compte de la diversité et des conflits afin de mieux faciliter une réponse juste et équitable à la crise climatique.

Changes in extreme precipitation indices across Algeria climate zones - Hamitouche, Yasmine; Zeroual, Ayoub; Meddi, Mohamed; Assani, Ali Arkamose; Alkama, Ramdane (International Journal of Climatology, 2024)
Abstract Extreme precipitation events can have a significant impact on the environment, agriculture, economy and safety, making close monitoring of their short‐ and long‐term trends essential for the development of effective mitigation and adaptation strategies. In this study, we analysed 16 in situ observation datasets from four different climate zones in Algeria, spanning from 1969 to 2021. The trend analysis was conducted using the original Mann–Kendall test and seven modified tests to eliminate the effects of short‐term persistence. Our findings reveal a significant increasing trend of extreme precipitation variability for most stations in the Warm Mediterranean climate zone, except for the Consecutive dry days index, which showed a negative trend for the same zone, while stations in the Cold/Warm semi‐arid climate and Cold desert climate (Bwk) zones showed a decreasing trend. Additionally, all index series with significant long‐term trends were affected by a significant shift in their means, which was confirmed by both the Lombard and Pettitt tests. However, when we used the modified MPT and the test eliminating the effects of long‐term persistence, the significance of the shifts and the trend decreased. Our results suggest that while extreme precipitation events have been increasing in some parts of Algeria; the trend may not be statistically significant in the long‐run, indicating the necessity of revisiting and refreshing the findings of previous studies for a more current perspective.
Keywords: Infolettre; Infolettre_Ete_2024; Site_internet_RIISQ

Development and validation of an index to measure progress in adaptation to climate change at the municipal level - Jacob, Johann; Valois, Pierre; Tessier, Maxime (Ecological Indicators, 2022)
Background Given the important role that municipalities must play in adapting to climate change, it is more than ever essential to measure their progress in this area. However, measuring municipalities’ adaptation progress presents its share of difficulties especially when it comes to comparing (on similar dimensions and over time) the situation of different municipal entities and to linking adaptation impacts to local actions. Longitudinal studies with recurring indicators could capture changes occurring over time, but the development of such indicators requires great emphasis on methodological and psychometric aspects, such as measurement validity. Therefore, this study aimed to develop and validate an index of adaptation to heatwaves and flooding at the level of municipal urbanists and urban planners. Methods A sample of 139 officers working in urbanism and urban planning for municipal entities in the province of Quebec (Canada) completed an online questionnaire. Developed based on a literature review and consultation of representatives from the municipal sector, the questionnaire measured whether the respondent’s municipal entity did or did not adopt the behaviors that are recommended in the scientific and gray literature to adapt to heatwaves and flooding. Results Results of the various metrological analyses (indicator reliability analysis, first order confirmatory factor analysis, concurrent validity analysis, and nomological validity assessment analysis) confirmed the validity of the index developed to measure progress in climate change adaptation at the municipal level. The first dimension of the index corresponds to preliminary measures that inform and prepare stakeholders for action (i.e., groundwork adaptation initiatives), whereas the second refers to measures that aim to concretely reduce vulnerability to climate change, to improve the adaptive capacity or the resilience of human and natural systems (i.e., adaptation actions). Conclusion The results of a series of psychometric analyses showed that the index has good validity and could properly measure the adoption of actions to prepare for adaptation as well as adaptation actions per se. Municipal and government officials can therefore consider using it to monitor and evaluate adaptation efforts at the municipal level.
Keywords: Infolettre; Infolettre_Avril_2022; Site_internet_RIISQ

Climate change through a poverty lens - Hallegatte, Stephane; Rozenberg, Julie (Nature Climate Change, 2017)

Evaluation of probable maximum snow accumulation: Development of a methodology for climate change studies. - Klein, Iris Maria; Rousseau, Alain N.; Frigon, Anne; Freudiger, Daphné; Gagnon, Patrick (Journal of Hydrology, 2016)
Summary Probable maximum snow accumulation (PMSA) is one of the key variables used to estimate the spring probable maximum flood (PMF). A robust methodology for evaluating the PMSA is imperative so the ensuing spring PMF is a reasonable estimation. This is of particular importance in times of climate change (CC) since it is known that solid precipitation in Nordic landscapes will in all likelihood change over the next century. In this paper, a PMSA methodology based on simulated data from regional climate models is developed. Moisture maximization represents the core concept of the proposed methodology; precipitable water being the key variable. Results of stationarity tests indicate that CC will affect the monthly maximum precipitable water and, thus, the ensuing ratio to maximize important snowfall events. Therefore, a non-stationary approach is used to describe the monthly maximum precipitable water. Outputs from three simulations produced by the Canadian Regional Climate Model were used to give first estimates of potential PMSA changes for southern Quebec, Canada. A sensitivity analysis of the computed PMSA was performed with respect to the number of time-steps used (so-called snowstorm duration) and the threshold for a snowstorm to be maximized or not. The developed methodology is robust and a powerful tool to estimate the relative change of the PMSA. Absolute results are in the same order of magnitude as those obtained with the traditional method and observed data; but are also found to depend strongly on the climate projection used and show spatial variability.
MAG ID: 2307215066
Keywords: Rousseau_Alain

Adaptive capacity and human cognition: The process of individual adaptation to climate change - Grothmann, Torsten; Patt, Anthony (Global Environmental Change-human and Policy Dimensions, 2005)
MAG ID: 2006647242

Understanding the role of climate change in disaster mortality: Empirical evidence from the Global South - Chapagain, Dipesh; Bharati, Luna; Mechler, Reinhard; K.C., Samir; Pflug, Georg Ch.; Borgemeister, Christian (2023)
Abstract Climatic disaster impacts, such as loss of human life as its most severe consequence, have been rising globally. Several studies argue that population growth is responsible for the rise, and the role of climate change is not evident. While disaster mortality is highest in low-income countries, existing studies focus mostly on developed countries. Here we address this impact attribution question in the context of the Global South using disaster-specific mixed-effects regression models. We show that the rise in landslide and flood mortality in a low-income country such as Nepal between 1992-2021 is primarily attributable to increased precipitation extremes. An increase in one standardized unit in maximum one-day precipitation increases flood mortality by 33%, and heavy rain days increase landslide mortality by 45%. Similarly, a one-unit increase in per capita income decreases landslide and flood mortality by 30% and 45%, respectively. Population density does not show significant effects.
MAG ID: 4315631914

Risk perception—A lens for understanding adaptive behaviour in the age of climate change? Narratives from the Global South - Dhar, Tapan; Bornstein, Lisa; Lizarralde, Gonzalo; Nazimuddin, S.M. (International Journal of Disaster Risk Reduction, 2023)
Keywords: Infolettre; Infolettre_Septembre_2023; Lizarralde_Gonzalo

The archaeology of climate change: The case for cultural diversity - Burke, Ariane; Peros, Matthew C.; Wren, Colin D.; Pausata, Francesco S. R.; Riel-Salvatore, Julien; Moine, Olivier; De Vernal, Anne; Kageyama, Masa; Boisard, Solène (Proceedings of the National Academy of Sciences, 2021)
Anthropogenic climate change is currently driving environmental transformation on a scale and at a pace that exceeds historical records. This represents an undeniably serious challenge to existing social, political, and economic systems. Humans have successfully faced similar challenges in the past, however. The archaeological record and Earth archives offer rare opportunities to observe the complex interaction between environmental and human systems under different climate regimes and at different spatial and temporal scales. The archaeology of climate change offers opportunities to identify the factors that promoted human resilience in the past and apply the knowledge gained to the present, contributing a much-needed, long-term perspective to climate research. One of the strengths of the archaeological record is the cultural diversity it encompasses, which offers alternatives to the solutions proposed from within the Western agro-industrial complex, which might not be viable cross-culturally. While contemporary climate discourse focuses on the importance of biodiversity, we highlight the importance of cultural diversity as a source of resilience.

Evaluation of the Impact of Climate Change on Runoff Generation in an Andean Glacier Watershed - Escanilla-Minchel, Rossana; Alcayaga, Hernán; Soto-Alvarez, Marco; Kinnard, Christophe; Urrutia, Roberto (Water, 2020)
Excluding Antarctica and Greenland, 3.8% of the world’s glacier area is concentrated in Chile. The country has been strongly affected by the mega drought, which affects the south-central area and has produced an increase in dependence on water resources from snow and glacier melting in dry periods. Recent climate change has led to an elevation of the zero-degree isotherm, a decrease in solid-state precipitation amounts and an accelerated loss of glacier and snow storage in the Chilean Andes. This situation calls for a better understanding of future water discharge in Andean headwater catchments in order to improve water resources management in glacier-fed populated areas. The present study uses hydrological modeling to characterize the hydrological processes occurring in a glacio-nival watershed of the central Andes and to examine the impact of different climate change scenarios on discharge. The study site is the upper sub-watershed of the Tinguiririca River (area: 141 km2), of which nearly 20% is covered by Universidad Glacier. The semi-distributed Snowmelt Runoff Model + Glacier (SRM+G) was forced with local meteorological data to simulate catchment runoff. The model was calibrated on even years and validated on odd years during the 2008–2014 period and found to correctly reproduce daily runoff. The model was then forced with downscaled ensemble projected precipitation and temperature series under the RCP 4.5 and RCP 8.5 scenarios, and the glacier adjusted using a volume-area scaling relationship. The results obtained for 2050 indicate a decrease in mean annual discharge (MAD) of 18.1% for the lowest emission scenario and 43.3% for the most pessimistic emission scenario, while for 2100 the MAD decreases by 31.4 and 54.2%, respectively, for each emission scenario. Results show that decreasing precipitation lead to reduced rainfall and snowmelt contributions to discharge. Glacier melt thus partly buffers the drying climate trend, but our results show that the peak water occurs near 2040, after which glacier depletion leads to reducing discharge, threatening the long-term water resource availability in this region.
Keywords: Kinnard_Christophe

Interface bureaucrats and the everyday remaking of climate interventions: Evidence from climate change adaptation in Zambia - Funder, Mikkel; Mweemba, Carol Emma (Global Environmental Change, 2019)
Keywords: Ouvrage_Collectif_Numéro1

Integrated assessment of climate change impact on surface runoff contamination by pesticides - Gagnon, Patrick; Sheedy, Claudia; Rousseau, Alain N.; Bourgeois, Gaétan; Chouinard, Gérald (Integrated Environmental Assessment and Management, 2016)
Pesticide transport by surface runoff depends on climate, agricultural practices, topography, soil characteristics, crop type, and pest phenology. To accurately assess the impact of climate change, these factors must be accounted for in a single framework by integrating their interaction and uncertainty. This paper presents the development and application of a framework to assess the impact of climate change on pesticide transport by surface runoff in southern Quebec (Canada) for the 1981-2040 period. The crop enemies investigated were: weeds for corn (Zea mays); and for apple orchard (Malus pumila), three insect pests (codling moth (Cydia pomonella), plum curculio (Conotrachelus nenuphar) and apple maggot (Rhagoletis pomonella)) and two diseases (apple scab (Venturia inaequalis) and fire blight (Erwinia amylovora)). A total of 23 climate simulations, 19 sites, and 11 active ingredients were considered. The relationship between climate and phenology was accounted for by bioclimatic models of the Computer Centre for Agricultural Pest Forecasting (CIPRA) software. Exported loads of pesticides were evaluated at the edge-of-field scale using the Pesticide Root Zone Model (PRZM), simulating both hydrology and chemical transport. A stochastic model was developed to account for PRZM parameter uncertainty. Results of this study indicate that for the 2011-2040 period, application dates would be advanced from 3 to 7 days on average with respect to the 1981-2010 period. However, the impact of climate change on maximum daily rainfall during the application window is not statistically significant, mainly due to the high variability of extreme rainfall events. Hence for the studied sites and crop enemies considered, climate change impact on pesticide transported in surface runoff is not statistically significant throughout the 2011-2040 period.
MAG ID: 1899643429
Keywords: Rousseau_Alain

Simulation of aquifer-peatland-river interactions under climate change - Bourgault, M. A.; Larocque, M.; Roy, M. (Hydrology Research, 2014)
Wetlands play an important role in preventing extreme low flows in rivers and groundwater level drawdowns during drought periods. This hydrological function could become increasingly important under a warmer climate. Links between peatlands, aquifers, and rivers remain inadequately understood. The objective of this study was to evaluate the hydrologic functions of the Lanoraie peatland complex in southern Quebec, Canada, under different climate conditions. This peatland complex has developed in the beds of former fluvial channels during the final stages of the last deglaciation. The peatland covers a surface area of ~76 km2 and feeds five rivers. Numerical simulations were performed using a steady-state groundwater flow model. Results show that the peatland contributes on average to 77% of the mean annual river base flow. The peatland receives 52% of its water from the aquifer. Reduced recharge scenarios (−20 and −50% of current conditions) were used as a surrogate of climate change. With these scenarios, the simulated mean head decreases by 0.6 and 1.6 m in the sand. The mean river base flow decreases by 16 and 41% with the two scenarios. These results strongly underline the importance of aquifer-peatland-river interactions at the regional scale. They also point to the necessity of considering the entire hydrosystem in conservation initiatives.
Keywords: Ouvrage_Collectif_Numéro1

Integrated assessment of localized SSP–RCP narratives for climate change adaptation in coupled human-water systems - Alizadeh, Mohammad Reza; Adamowski, Jan; Inam, Azhar (Science of The Total Environment, 2022)

Impacts of climate change on the hydrology of northern midlatitude cold regions - Aygün, Okan; Kinnard, Christophe; Campeau, Stéphane (Progress in Physical Geography: Earth and Environment, 2020)
Cold region hydrology is conditioned by distinct cryospheric and hydrological processes. While snowmelt is the main contributor to both surface and subsurface flows, seasonally frozen soil also influences the partition of meltwater and rain between these flows. Cold regions of the Northern Hemisphere midlatitudes have been shown to be sensitive to climate change. Assessing the impacts of climate change on the hydrology of this region is therefore crucial, as it supports a significant amount of population relying on hydrological services and subjected to changing hydrological risks. We present an exhaustive review of the literature on historical and projected future changes on cold region hydrology in response to climate change. Changes in snow, soil, and streamflow key metrics were investigated and summarized at the hemispheric scale, down to the basin scale. We found substantial evidence of both historical and projected changes in the reviewed hydrological metrics. These metrics were shown to display different sensitivities to climate change, depending on the cold season temperature regime of a given region. Given the historical and projected future warming during the 21st century, the most drastic changes were found to be occurring over regions with near-freezing air temperatures. Colder regions, on the other hand, were found to be comparatively less sensitive to climate change. The complex interactions between the snow and soil metrics resulted in either colder or warmer soils, which led to increasing or decreasing frost depths, influencing the partitioning rates between the surface and subsurface flows. The most consistent and salient hydrological responses to both historical and projected climate change were an earlier occurrence of snowmelt floods, an overall increase in water availability and streamflow during winter, and a decrease in water availability and streamflow during the warm season, which calls for renewed assessments of existing water supply and flood risk management strategies.
Keywords: Kinnard_Christophe

Investigation of the Multi-Scale Deterioration Mechanisms of Anhydrite Rock Exposed to Freeze–Thaw Environment - Jin, Xiaoguang; Hou, Chao; He, Jie; Dias, Daniel (Materials, 2024)
The deterioration of anhydrite rock exposed to a freeze–thaw environment is a complex process. Therefore, this paper systematically investigated the physical and mechanical evolutions of freeze–thawed anhydrite rock through a series of multi-scale laboratory tests. Meanwhile, the correlation between pore structure and macroscopic mechanical parameters was discussed, and the deterioration mechanisms of anhydrite rock under freeze–thaw cycles were revealed. The results show that with the increase in freeze–thaw processes, the mechanical strength, elastic modulus, cohesion, proportions of micropores (r ≤ 0.1 μm), and PT-Ipore throat (0–0.1 μm) decrease exponentially. In comparison, the mass variation, proportions of mesopores (0.1 μm < r < 1 μm), macropores (r ≥ 1 μm), and PT-II pore throat (0.1–4 μm) increase exponentially. After 120 cycles, the mean porosity increases by 66.27%, and there is a significant honeycomb and pitted surface phenomenon. Meanwhile, as the freeze–thaw cycles increase, the frost resistance coefficient decreases, while the damage variable increases. The correlation analysis between pore structure and macroscopic mechanical parameters shows that macropores play the most significant role in the mechanical characteristic deterioration of freeze–thawed anhydrite rock. Finally, it is revealed that the water–rock expansion and water dissolution effects play a crucial role in the multi-scale damage of anhydrite rock under the freeze–thaw environment.
Keywords: Infolettre; Infolettre_Fevrier_2024

Fine‐scale environment control on ground surface temperature and thaw depth in a High Arctic tundra landscape - Khani, Hadi Mohammadzadeh; Kinnard, Christophe; Gascoin, Simon; Lévesque, Esther (Permafrost and Periglacial Processes, 2023)
Abstract Surface conditions are known to mediate the impacts of climate warming on permafrost. This calls for a better understanding of the environmental conditions that control the thermal regime and the depth of the active layer, especially within heterogeneous tundra landscapes. This study analyzed the spatial relationships between thaw depths, ground surface temperature (GST), and environmental conditions in a High Arctic tundra environment at Bylot Island, Nunavut, Canada. Measurements were distributed within the two dominant landforms, namely earth hummocks and low‐center polygons, and across a topographic gradient. Our results revealed that GST and thaw depth were highly heterogeneous, varying by up to 3.7°C and by more than 20 cm over short distances (<1 m) within periglacial landforms. This microscale variability sometimes surpassed the variability at the hillslope scale, especially in summer. Late‐winter snowpack thickness was found to be the prime control on the spatial variability in winter soil temperatures due to the highly heterogeneous snow cover induced by blowing snow, and this thermal effect carried over into summer. However, microtopography was the predominant driver of the spatial variability in summer GST, followed by altitude and moss thickness. In contrast, the spatial variability in thaw depth was influenced predominantly by variations in moss thickness. Hence, summer microclimate conditions dominated active layer development, but a thicker snowpack favored soil cooling in the following summer, due to the later disappearance of snow cover. These results enhance our understanding of High Arctic tundra environments and highlight the complexity of considering surface feedback effects in future projections of permafrost states within heterogeneous tundra landscapes.
Keywords: Kinnard_Christophe

Evaluating Operational Risk in Environmental Modeling: Assessment of Reliability and Sharpness for Ensemble Selection - Pokorny, Scott; Stadnyk, Tricia A.; Ali, Genevieve (Journal of Hydrologic Engineering, 2023)

Ice Nucleation of Pharmaceutical and Synthetic Organic Emerging Contaminants: The Impact of Selected Environmental Conditions - Kaur, Japandeep; Ganguly, Mainak; Rangel-Alvardo, Rodrigo; Pal, Devendra; Hall, Ryan; Ariya, Parisa A. (ACS Earth and Space Chemistry, 2022)

Risks and the Anthropocene: Alternative Views on the Environmental Emergency - Rebotier, J (Wiley, 2022)
Keywords: Nobert_Sebastien

Hydrological behaviour of an ice‐layered snowpack in a non‐mountainous environment - Paquotte, Andrea; Baraer, Michel (Hydrological Processes, 2022)
Abstract The increased frequency of mild rain‐on‐snow (R.O.S.) events in cold regions associated with climate change is projected to affect snowpack structure and hydrological behaviour. The ice layers that form in a cold snowpack when R.O.S. events occur have been shown to influence flowthrough processes and liquid water retention, with consequences for winter floods, groundwater recharge, and water resources management. This study explores interconnections between meteorological conditions, ice layer formation, and lateral flows during R.O.S. events throughout the 2018–2019 winter in meridional Quebec, Canada. Automated hydro‐meteorological measurements, such as water availability for runoff, snow water equivalent, and snowpit observations, are used to compute water and energy balances, making it possible to characterize a snowpack's internal conditions and flowthrough regimes. For compatibility assessment, water and energy balances‐based flowthrough scenarios are then compared to different hydro‐meteorological variables', such as water table or streamlet water levels. The results show an association between highly variable meteorological conditions, frequent R.O.S. events, and ice layer formation. Lateral flows were mainly observed during the early stage of the ablation period. The hydrologically significant lateral flows observed in the study are associated with winter conditions that are predicted to become more frequent in a changing climate, stressing the need for further evaluation of their potential impact at the watershed scale.
Keywords: Baraer_Michel; Infolettre; Infolettre_Ete_2023

Evaluating the Ubiquity of Thresholds in Rainfall‐Runoff Response Across Contrasting Environments - Ross, Cody A.; Ali, Geneviève A.; Spence, Christopher; Courchesne, François (Water Resources Research, 2021)
Abstract Thresholds in precipitation‐runoff relationships have been observed in numerous studies using scatter plots comparing meteorological factors and hydrologic response metrics. Most thresholds reported in the literature have been identified from relationships between meteorological factors that quantify volumes or depths of water (e.g., total event rainfall) and metrics capturing hydrologic response magnitude (e.g., runoff ratio), with a strong emphasis on hillslopes and catchments in temperate humid environments. Knowledge gaps, however, remain regarding the ubiquity of hydrologic thresholds across different climatic environments and different meteorological factors that affect different response metrics. This study therefore aimed to evaluate relationships for a wide range of meteorological factors and response metrics derived from event‐scale rainfall‐runoff analysis for 21 sites spanning seven contrasting geographic areas. Specifically, meteorological factors quantifying rainfall depth, rainfall intensity, and hydrologic abstractions related to evapotranspiration were considered, along with response metrics that describe response timing and response magnitude, leading to 4,557 relationships being evaluated. While rainfall depth thresholds were observed for most sites, rainfall intensity thresholds were also observed. Additionally, threshold behavior was shown to be sensitive to antecedent conditions over specific durations of time preceding a rainfall‐runoff event. The large number of relationships evaluated in this study allowed for the development of a typology of threshold dynamics and the formulation of hypotheses about dominant hydrological processes. This typology may not only promote standardized threshold descriptions but also make intersite comparisons of nonlinear rainfall‐runoff behavior easier. , Key Points While water volume thresholds dominate the literature, rainfall intensity thresholds were observed even at sites with humid climates Threshold behavior is sensitive to antecedent conditions over specific durations of time preceding a rainfall‐runoff event A newly proposed typology of threshold dynamics may be used toward standardized threshold descriptions and intersite comparisons

A New Dynamical Core of the Global Environmental Multiscale (GEM) Model with a Height-Based Terrain-Following Vertical Coordinate - Husain, Syed Zahid; Girard, Claude; Qaddouri, Abdessamad; Plante, André (Monthly Weather Review, 2019)
Abstract A new dynamical core of Environment and Climate Change Canada’s Global Environmental Multiscale (GEM) atmospheric model is presented. Unlike the existing log-hydrostatic-pressure-type terrain-following vertical coordinate, the proposed core adopts a height-based approach. The move to a height-based vertical coordinate is motivated by its potential for improving model stability over steep terrain, which is expected to become more prevalent with the increasing demand for very high-resolution forecasting systems. A dynamical core with height-based vertical coordinate generally requires an iterative solution approach. In addition to a three-dimensional iterative solver, a simplified approach has been devised allowing the use of a direct solver for the new dynamical core that separates a three-dimensional elliptic boundary value problem into a set of two-dimensional independent Helmholtz problems. The issue of dynamics–physics coupling has also been studied, and incorporating the physics tendencies within the discretized dynamical equations is found to be the most acceptable approach for the height-based vertical coordinate. The new dynamical core is evaluated using numerical experiments that include two-dimensional nonhydrostatic theoretical cases as well as 25-km resolution global forecasts. For a wide range of horizontal grid resolutions—from a few meters to up to 25 km—the results from the direct solution approach are found to be equivalent to the iterative approach for the new dynamical core. Furthermore, results from the different numerical experiments confirm that the new height-based dynamical core is equivalent to the existing pressure-based core in terms of solution accuracy.

Global Meta‐Analysis on the Relationship Between Mercury and Dissolved Organic Carbon in Freshwater Environments - Lavoie, Raphael A.; Amyot, Marc; Lapierre, Jean‐François (Journal of Geophysical Research: Biogeosciences, 2019)
Abstract In freshwater ecosystems, several studies have shown a strong linear relationship between total mercury (THg) or methylmercury (MeHg) and dissolved organic carbon (DOC) concentrations. Variations in this linear relationship have been reported, but the magnitude and causes of this variation are not well known. The objective of this study was to conduct a meta‐analysis to quantify and understand the global variation of this mercury (Hg)–DOC association. This meta‐analysis included 54 studies in lentic and lotic ecosystems for a total of 85 THg–DOC and 59 MeHg–DOC relationships. There was an increase in Hg with DOC concentrations in water with a global average slope of 0.25 (confidence interval (CI): 0.20–0.35) ng/mg for THg and 0.029 (CI: 0.014–0.044) ng/mg for MeHg. Relationships were stronger for (1) North American studies, (2) natural environments compared to those disturbed by anthropogenic activities, (3) spatial studies compared to temporal studies, (4) filtered samples (THg only), and (5) the aromatic fraction of DOC compared to the bulk DOC. Coupling with DOC was stronger for THg than for MeHg. Ecosystem type (lentic vs. lotic), geographical coordinates, and publication year did not influence the strength of relationships. Overall, we show that there is a strong but variable coupling between carbon and mercury cycles in freshwater ecosystems globally and that this link is modulated regionally by geographic location, temporal scale, and human activity, with implications for understanding these rapidly changing biogeochemical processes in response to global change. , Plain Language Summary In lakes and rivers, organic carbon is known to be a transporter of mercury, a toxic metal. However, depending on the chemistry of waterbodies, carbon can carry different amounts of mercury. This work compiled results of 54 scientific studies around the world looking at the correlation between mercury and organic carbon. We looked at the conditions that make this relationship vary. We found that relationships were almost always positive and that the type of carbon influenced the amount of mercury that was carried. The strength of those relationships was higher in natural ecosystems compared to those with human influence and in North American ecosystems compared to European and Asian ones. This work is important to understand the mechanism behind the association between mercury and carbon in different environments and how carbon can be used to explain variations in mercury, especially in a changing climate under human pressure. , Key Points Mercury and dissolved organic matter coupling is stronger in spatial studies, in North America, in natural systems, and in filtered samples Correlations are stronger with the aromatic fraction than the bulk dissolved organic carbon and stronger for total than methyl mercury Ecosystem type (lentic vs. lotic), geographical coordinates, and publication year had no effect on the strength of relationships

Challenges in evaluating strategies for reducing a building's environmental impact through Integrated Design - Leoto, Ricardo; Lizarralde, Gonzalo (Building and Environment, 2019)
Keywords: Lizarralde_Gonzalo

Examining the challenges of simulating surface water–groundwater interactions in a post-glacial environment - Turgeon, Félix; Larocque, Marie; Meyzonnat, Guillaume; Dorner, Sarah; Bourgault, Marc-André (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2018)
Keywords: Dorner_Sarah

Cumulative Effects of Watershed Disturbances and Run-of-river Dams on Mercury Cycling: Case Study and Recommendations for Environmental Managers - Amyot, M.; Bilodeau, F.; Tremblay, A.; Planas, D.; Walsh, D.; Ponton, D. E. (Environmental Management, 2024)
Abstract Run-of-river power plants (ROR) represent the majority of hydroelectric plants worldwide. Their environmental impacts are not well documented and are believed to be limited, particularly regarding the contamination of food webs by methylmercury (MeHg), a neurotoxin. RORs are typically installed in small rivers where combined effects of watershed disturbances with dam construction can complicate environmental management. We report a multi-year case study on the Saint-Maurice River (Canada) where an unpredicted temporary increase in MeHg accumulation in predator fish was observed after the construction of two ROR plants. The associated pondages acted as sedimentation basins for mercury (Hg) and organic matter from a watershed disturbed by a forest fire and by logging. This fresh organic carbon likely fueled microbial MeHg production. Hg methylation was more associated with environmental conditions than to the presence of Hg, and main methylating microbial groups were identified. A constructed wetland was a site of significant Hg methylation but was not the main source of the fish Hg increase. Organic carbon degradation was the main driver of MeHg accumulation at the base of the food chain whereas trophic levels explained the variations at the top of the food chain. Overall, carbon cycling was a key driver of Hg dynamics in this system, and ROR plants can cause temporary (ca. 12 years) Hg increase in food webs when developed in disturbed watersheds, although this increase is smaller than for large reservoirs. Recommendations for future ROR construction are to establish a good environmental monitoring plan with initial high temporal resolution and to consider recent and potential watershed disturbances in the plan.

Experimental and Numerical Simulation Investigation of the Mechanical Properties of Anhydrite Rock Under Freeze–Thaw Environment - Hou, Chao; Jin, Xiaoguang; Zhai, Shengtian; He, Jie; Lei, Ruide; Dias, Daniel (Geotechnical and Geological Engineering, 2024)
To study the mechanical and cracking modes of anhydrite rock under the freeze–thaw weathering process, the physico-mechanical characteristics and morphology evolutions of anhydrite samples were determined by a series of laboratory tests. Then, a numerical simulation model was established through the PFC2D program, and the types and number of cracks during the uniaxial compression conditions were analyzed. Finally, the distribution of maximum principal stress and shear stress was revealed. The results indicate that as the number of freeze–thaw cycles increases, there is a growth in the mass loss rate and macroscopic damage variables while the uniaxial compression strength and elastic modulus decrease exponentially. Under uniaxial compression stress, the proportion of tensile cracks in the anhydrite model is the highest, followed by tensile shear cracks and compressive shear cracks. As the number of freeze–thaw cycles increases, the proportion of tensile cracks increases exponentially, while the proportion of tensile shear cracks and compressive shear cracks decreases exponentially. Furtherly, it is found that the maximum principal stress and maximum shear stress extreme values decrease exponentially with the increase of freeze–thaw cycles. For example, after 120 cycles, the maximum shear stress at the peak stress point decreased by 47.3%. The research results will promote the comprehension of anhydrite rock geotechnical engineering disaster mechanisms in cold regions.
Keywords: Infolettre; Infolettre_Mai_2024

Topographic and vegetation controls of the spatial distribution of snow depth in agro-forested environments by UAV lidar - Dharmadasa, Vasana; Kinnard, Christophe; Baraër, Michel (The Cryosphere, 2023)
Abstract. Accurate knowledge of snow depth distributions in forested regions is crucial for applications in hydrology and ecology. In such a context, understanding and assessing the effect of vegetation and topographic conditions on snow depth variability is required. In this study, the spatial distribution of snow depth in two agro-forested sites and one coniferous site in eastern Canada was analyzed for topographic and vegetation effects on snow accumulation. Spatially distributed snow depths were derived by unmanned aerial vehicle light detection and ranging (UAV lidar) surveys conducted in 2019 and 2020. Distinct patterns of snow accumulation and erosion in open areas (fields) versus adjacent forested areas were observed in lidar-derived snow depth maps at all sites. Omnidirectional semi-variogram analysis of snow depths showed the existence of a scale break distance of less than 10 m in the forested area at all three sites, whereas open areas showed comparatively larger scale break distances (i.e., 11–14 m). The effect of vegetation and topographic variables on the spatial variability in snow depths at each site was investigated with random forest models. Results show that the underlying topography and the wind redistribution of snow along forest edges govern the snow depth variability at agro-forested sites, while forest structure variability dominates snow depth variability in the coniferous environment. These results highlight the importance of including and better representing these processes in physically based models for accurate estimates of snowpack dynamics.
Keywords: Baraer_Michel; Kinnard_Christophe

An Accuracy Assessment of Snow Depth Measurements in Agro-Forested Environments by UAV Lidar - Dharmadasa, Vasana; Kinnard, Christophe; Baraër, Michel (Remote Sensing, 2022)
This study assesses the performance of UAV lidar system in measuring high-resolution snow depths in agro-forested landscapes in southern Québec, Canada. We used manmade, mobile ground control points in summer and winter surveys to assess the absolute vertical accuracy of the point cloud. Relative accuracy was determined by a repeat flight over one survey block. Estimated absolute and relative errors were within the expected accuracy of the lidar (~5 and ~7 cm, respectively). The validation of lidar-derived snow depths with ground-based measurements showed a good agreement, however with higher uncertainties observed in forested areas compared with open areas. A strip alignment procedure was used to attempt the correction of misalignment between overlapping flight strips. However, the significant improvement of inter-strip relative accuracy brought by this technique was at the cost of the absolute accuracy of the entire point cloud. This phenomenon was further confirmed by the degraded performance of the strip-aligned snow depths compared with ground-based measurements. This study shows that boresight calibrated point clouds without strip alignment are deemed to be adequate to provide centimeter-level accurate snow depth maps with UAV lidar. Moreover, this study provides some of the earliest snow depth mapping results in agro-forested landscapes based on UAV lidar.
MAG ID: 4221028823
Keywords: Baraer_Michel; Kinnard_Christophe

Greening the color line: historicizing water infrastructure redevelopment and environmental justice in the St. Louis metropolitan region - Heck, Sarah (Journal of Environmental Policy & Planning, 2021)

Ice Nucleation of Model Nanoplastics and Microplastics: A Novel Synthetic Protocol and the Influence of Particle Capping at Diverse Atmospheric Environments - Ganguly, Mainak; Ariya, Parisa A. (ACS Earth and Space Chemistry, 2019)

Lower Respiratory Symptoms Associated With Environmental and Reconstruction Exposures After Hurricane Sandy - Gargano, Lisa M.; Locke, Sean; Jordan, Hannah T.; Brackbill, Robert M. (Disaster Medicine and Public Health Preparedness, 2018)
Abstract Objective In a population with prior exposure to the World Trade Center (WTC) disaster, this study sought to determine the relationship between Hurricane Sandy-related inhalation exposures and post-Sandy lower respiratory symptoms (LRS). Methods Participants included 3835 WTC Health Registry enrollees who completed Wave 3 (2011-2012) and Hurricane Sandy (2013) surveys. The Sandy-related inhalational exposures examined were: (1) reconstruction exposure; (2) mold or damp environment exposure; and (3) other respiratory irritants exposure. LRS were defined as wheezing, persistent cough, or shortness of breath reported on ≥1 of the 30 days preceding survey completion. Associations between LRS and Sandy exposures, controlling for socio-demographic factors, post-traumatic stress disorder, and previously reported LRS and asthma were examined using multiple logistic regression. Results Over one-third of participants (34.4%) reported post-Sandy LRS. Each of the individual exposures was also independently associated with post-Sandy LRS, each having approximately twice the odds of having post-Sandy LRS. We found a dose-response relationship between the number of types of Sandy-related exposures reported and post-Sandy LRS. Conclusions This study provides evidence that post-hurricane clean-up and reconstruction exposures can increase the risk for LRS. Public health interventions should emphasize the importance of safe remediation practices and recommend use of personal protective equipment. ( Disaster Med Public Health Preparedness . 2018;12:697-702)
Keywords: Ouvrage_Collectif_Numéro1

Using the ecosystem serviceshed concept in conservation planning for more equitable outcomes - Goyette, Jean-Olivier; Mendes, Poliana; Cimon-Morin, Jérôme; Dupras, Jérôme; Pellerin, Stéphanie; Rousseau, Alain N.; Poulin, Monique (Ecosystem Services, 2024)
Keywords: Infolettre; Infolettre_Avril_2024

Differing Modes of Biotic Connectivity within Freshwater Ecosystem Mosaics - Mushet, David M.; Alexander, Laurie C.; Bennett, Micah; Schofield, Kate; Christensen, Jay R.; Ali, Genevieve; Pollard, Amina; Fritz, Ken; Lang, Megan W. (JAWRA Journal of the American Water Resources Association, 2019)
Abstract We describe a collection of aquatic and wetland habitats in an inland landscape, and their occurrence within a terrestrial matrix, as a “freshwater ecosystem mosaic” (FEM). Aquatic and wetland habitats in any FEM can vary widely, from permanently ponded lakes, to ephemerally ponded wetlands, to groundwater‐fed springs, to flowing rivers and streams. The terrestrial matrix can also vary, including in its influence on flows of energy, materials, and organisms among ecosystems. Biota occurring in a specific region are adapted to the unique opportunities and challenges presented by spatial and temporal patterns of habitat types inherent to each FEM. To persist in any given landscape, most species move to recolonize habitats and maintain mixtures of genetic materials. Species also connect habitats through time if they possess needed morphological, physiological, or behavioral traits to persist in a habitat through periods of unfavorable environmental conditions. By examining key spatial and temporal patterns underlying FEMs, and species‐specific adaptations to these patterns, a better understanding of the structural and functional connectivity of a landscape can be obtained. Fully including aquatic, wetland, and terrestrial habitats in FEMs facilitates adoption of the next generation of individual‐based models that integrate the principles of population, community, and ecosystem ecology. , Research Impact Statement : Fully including aquatic, wetland, and terrestrial habitats facilitates adoption of next‐generation, individual‐based, models that integrate principles of population, community, and ecosystem ecology.

Bloated bodies and broken bricks: Power, ecology, and inequality in the political economy of natural disaster recovery - Sovacool, Benjamin K.; Tan-Mullins, May; Abrahamse, Wokje (World Development, 2018)

Fardeau actuel et futur de la maladie de Lyme au Québec en fonction des changements climatiques - Ripoche, Marion; Irace-Cima, Alexandra; Adam-Poupart, Ariane; Baron, Geneviève; Bouchard, Catherine; Carignan, Alex; Milord, François; Ouhoummane, Najwa; Pilon, Pierre; Thivierge, Karine; Zinszer, Kate; Chaumont, Diane (Relevé des maladies transmissibles au Canada, 2023)

Vagues de chaleur en contexte de changements climatiques - Annexe 2 - Projet CASSSIOPÉE - Turmel, J.; Lafond, A.; Lessard, L. (2023)

Rapport final sur le développement de courbes de géométrie hydraulique adaptées à différents contextes physiographiques au Québec présenté au Ministère de l’Environnement et de la Lutte contre les changements climatiques, de la Faune et des Parcs (MELCCFP) - Boulet, Y.; Boivin, M.; Biron, P. (Laboratoire d’expertise et de recherche en géographie appliquée (LERGAUQAC), 2023)
Keywords: Boivin_Maxime

Influence des variables météorologiques et des changements climatiques sur l’occurrence, la fréquence et la magnitude des mouvements de versant (avalanche de neige, chute de blocs de glace et chute de pierre) affectant certains tronçons des routes 132 et 198 dans le nord de la Gaspésie - Gauthier, F.; Laliberté, J.; Birien, T.; Boulet, Y.; Meloche, F.; Buffin-Bélanger, T. (Laboratoire de géomorphologie et de gestion des risques en montagne (LGGRM), Université du Québec à Rimouski, 2022)

Le Québec récemment frappé par les crues extrêmes : une manifestation des changements climatiques ? - Leconte, Robert (Le Climatoscope, 2019)
Les printemps 2017 et 2019 auront frappé l’imaginaire collectif en raison de l’ampleur des crues ayant touché de nombreuses rivières du Québec et des dommages qui leur sont associés. En 2019, près de 6700 résidences localisées dans 51 municipalités et distribuées dans presque toutes les principales régions du Québec ont été inondées, sans compter les nombreuses autres résidences qui se sont retrouvées isolées en raison de routes submergées et de glissements de terrain. Le bilan en 2017 était similaire, avec 5371 maisons inondées dans 261 municipalités et 4066 personnes évacuées. Les débits dans plusieurs rivières ont excédé les valeurs mesurées depuis que les stations de jaugeage ont été installées. À titre d’exemple, en 2019, le débit journalier dans la rivière Rouge à la hauteur du Barrage de la Chute-Bell, où Hydro-Québec a craint pour la stabilité de l’ouvrage, a atteint 975 m3/s, la plus forte valeur jamais enregistrée depuis 1964. Une analyse statistique révèle qu’un tel débit a une chance d’être dépassé en moyenne une fois tous les 175 ans. Il s’agit d’un événement exceptionnel. Pourtant, un autre événement extrême se produisait au même endroit en 1998, cette fois-ci avec un débit maximal journalier de 914 m3/s. Deux crues printanières majeures en 20 ans : est-ce la conséquence des changements climatiques ? Cet article propose une genèse des événements hydrologiques extrêmes, puis présente des projections climatiques aux horizons 2050 et 2080 pour différentes rivières au Sud et au Nord du fleuve Saint-Laurent. Puis, est exposée la démarche générale employée pour caractériser le régime hydrologique des bassins versants en climat futur.
Keywords: Ouvrage_Collectif_Numéro1

Vers l’adaptation. Synthèse des connaissances sur les changements climatiques au Québec. Partie 1 : Évolution climatique au Québec - Ouranos (Ouranos, 2015)
Keywords: Ouvrage_Collectif_Numéro1

Espace de liberté: un cadre de gestion intégrée pour la conservation des cours d’eau dans un contexte de changements climatiques - Biron, P.; Buffin-Bélanger, T.; Larocque, M.; Demers, S.; Olsen, T.; Ouellet, M.-A.; Choné, G.; Cloutier, C.-A.; Needelman, M. (OURANOS, 2013)
Les changements climatiques anticipés produiront des crues plus fréquentes et des étiages plus prononcés qui menaceront la sécurité publique et l’état des écosystèmes fluviaux. L’espace de liberté des cours d’eau est un cadre de gestion intégrée considérant l’hydrogéomorphologie des rivières. Il vise à identifier des espaces d’inondabilité et de mobilité du cours d’eau où on accepte de le laisser évoluer plutôt que de le contraindre dans un tracé façonné par les interventions anthropiques. Cette approche apparaît prometteuse pour une gestion durable dans un climat changeant, car elle maintient les fonctions physiques naturelles des cours d’eau (transport de l’eau et des sédiments), ce qui augmente leur résilience. L’espace de liberté reconnaît aussi le rôle majeur de la connectivité entre la rivière et la nappe phréatique, notamment par l'entremise des milieux humides qui contribuent à l’atténuation des crues et des étiages et à une amélioration de la qualité de l’eau. Les objectifs de ce projet consistent à 1) développer l’approche de gestion des cours d’eau basée sur les concepts d’espace de liberté pour les cours d’eau du Québec et examiner sa mise en œuvre pour renforcer la capacité de résilience des rivières dans un contexte de changements climatiques; 2) évaluer la connectivité entre la rivière et la nappe afin de mieux comprendre le rôle des milieux humides dans l'espace de liberté des cours d’eau et 3) effectuer une analyse avantages-coûts de l’implantation d’un espace de liberté. L’espace de liberté a été déterminé par l’approche hydrogéomorphologique et cartographié pour trois cours d’eau contrastés du Québec (rivières de la Roche et Yamaska Sud-Est en Montérégie et rivière Matane en Gaspésie). La démarche consiste 1) d’une analyse de photographies historiques anciennes, de modèles numériques d’altitude et d’observations sur le terrain; 2) de mesures simultanées des niveaux et des températures de la nappe phréatique et du cours d’eau et 3) de simulations numériques pour estimer l’impact des changements climatiques sur la mobilité et l’inondabilité des cours d’eau. La méthodologie développée pour définir l’espace de liberté est robuste et s’applique tant pour les cours d’eau agricoles (rivière de la Roche et Yamaska Sud-Est) que pour les rivières à saumon plus dynamiques comme la rivière Matane. L’espace de liberté inclut trois niveaux d’inondabilité (N1 : très fréquente et/ou avec forts courants, N2 : fréquente de faible courant, N3 : peu fréquente), deux niveaux de mobilité (M1 : à court terme (50 ans) et M2 : basée sur l’amplitude des méandres), ainsi que les milieux humides. Les analyses de sensibilité par simulation numérique révèlent que les limites de l’espace de liberté intègrent adéquatement la mobilité et l’inondabilité attendues dans un climat futur. Une cartographie simplifiée de l’espace de liberté, à deux niveaux, est également produite. L’espace de liberté minimal (L1) inclut les inondations très fréquentes (N1), les milieux humides riverains ainsi que la mobilité à court terme (M1). C’est une zone où il ne devrait pas y avoir d’aménagement. La zone L2 représente quant à elle l’espace fonctionnel de la rivière (N2 et M2) qui devrait être protégé afin que la dynamique naturelle de la rivière puisse opérer en climat actuel et futur. Les aménagements dans cette zone devraient tenir compte des risques d’érosion et d’inondation. Les résultats de l’analyse avantages-coûts suggèrent que l’aménagement d’espaces de liberté serait économiquement avantageux pour les trois cours d’eau. Malgré la perte du droit de construire et de cultiver dans l’espace de liberté, accompagnée par une compensation financière pour les agriculteurs, des gains nets variant entre 0,7 et 3,7 millions de dollars sont estimés sur une période de 50 ans. Ceci est dû aux réductions des coûts de protection des berges déjà stabilisées et qui le seraient à l’avenir, mais aussi aux services écologiques rendus par les milieux humides et les bandes riveraines. Une gestion par espace de liberté des cours d’eau du Québec exige un changement majeur dans nos perceptions et nos représentations des rivières qui, jusqu’à maintenant, ont été considérées comme des entités relativement statiques dans le paysage. Une telle approche apportera notamment comme avantage de faciliter l’adaptation aux risques liés à une plus grande variabilité des débits en climat futur par une gestion proactive qui améliore la santé des cours d’eau tout en étant avantageuse économiquement à moyen et à long terme. Elle contribuera également à diminuer les risques pour les infrastructures et la sécurité publique en utilisant une cartographie basée sur la dynamique des cours d’eau pour déterminer les zones où les aménagements devraient être interdits à l’avenir.
Keywords: Ouvrage_Collectif_Numéro1

Données du Réseau de surveillance du climat du Québec - Ministère de l’Environnement et de la Lutte contre les changements climatiques (MELCC) (2020)

Quarante ans de participation publique en environnement, aménagement du territoire et urbanisme au Québec : entre expression des conflits et gestion consensuelle - Bherer, Laurence; Gauthier, Mario; Simard, Louis (Cahiers de géographie du Québec, 2019)
En près de 40 ans, les revendications pour plus de participation et de transparence, ainsi que la diffusion du principe de développement durable ont profondément transformé les secteurs de l’environnement, de l’aménagement du territoire et de l’urbanisme. Au fil des décennies, divers types de dispositifs de participation publique ont vu le jour dans ces deux secteurs d’activité qui ont permis de démocratiser le rapport gouvernants / gouvernés et la relation entre les pouvoirs publics et la société civile. À partir d’une grille d’analyse axée sur deux dimensions – ouverture / fermeture et antagoniste / consensuel – nous analysons les différents dispositifs de participation publique à l’oeuvre dans ces deux secteurs. L’analyse tend à montrer que : 1) au cours des 40 dernières années, les dispositifs participatifs se sont multipliés ; 2) aux dispositifs participatifs traditionnels permettant l’expression des conflits et des oppositions se sont progressivement ajoutés des dispositifs davantage orientés vers la recherche du consensus et la résolution des conflits ; 3) de nos jours, ces deux grandes catégories de dispositifs cohabitent et peuvent parfois apparaître comme étant complémentaires et parfois comme étant contradictoires. , Over the past 40 years, demands for greater participation, transparency and the dissemination of the principle of sustainable development have transformed the areas of environment, land-use planning and urban planning. Over the decades, various types of public participation mechanisms have emerged in these sectors that helped democratize the rulers / governed report and the relationship between public authorities and civil society. Starting from a grid analysis based on two dimensions—opening / closing and antagonist / consensus—this article analyses the different public participation mechanisms at work in these two areas. Analysis tends to demonstrate that during the last forty years the number of participatory mechanisms has increased. Moreover, devices oriented towards the search for consensus and conflict resolution were gradually added to the traditional participatory mechanisms that allowed for the voicing of concerns and oppositions. Currently, these two broad categories of participatory tools coexist and can at times appear complementary and at others contradictory. , En casi cuarenta años, las reivindicaciones de mayor participación y transparencia, tanto como la difusión del principio de desarrollo sostenido, han transformado profundamente los sectores del medio ambiente, de la planificación territorial y del urbanismo. Con el correr de las décadas, varios tipos de dispositivos de participación pública surgieron en esos dos sectores de actividad que permitieron democratizar la relación gobernantes / gobernados y la relación poderes públicos y la sociedad civil. Gracias a una tabla de análisis con dos coordenadas – apertura / cierre y antagonista / consensual – analizamos diferentes dispositivos de participación pública que actúan en esos dos sectores. El análisis propone que: 1) durante los últimos cuarenta años, los dispositivos de participación han aumentado. 2) A los dispositivos participativos tradicionales que permiten la expresión de conflictos y oposiciones, se añadieron progresivamente dispositivos mejor orientados hacia la busqueda de consenso y de solución de conflictos. 3) Hoy, esas dos grandes categorías de dispositivos cohabitan y hasta parecen unas veces complementarias y otras contradictorias.
Keywords: Ouvrage_Collectif_Numéro1

Speculative Political Ecologies: (re)imagining urban futures of climate extremes - Rusca, Maria; Barcena, Alejandro; Savelli, Elisa; Messori, Gabriele (Journal of Political Ecology, 2023)
What role can a speculative political ecology play in (re)imaging urban futures of climate extremes? In recent years, narratives of dystopian futures of climate extremes have proliferated in geosciences, and across the media and creative arts. These anxiety-fueled narratives often generate a sense of resignation and unavoidability, which contributes to foreclosing the possibility of radically different political projects. In this article, we argue that these narratives conceal the coproduction of nature and society and treat nature as the problem, thereby locking futures into dystopic configurations. Political ecology scholarship can contribute to generate a politics of possibility by reconceptualizing the relations that constitute urban futures under climate extremes as socionatural. This, we argue, calls for a more experimental political ecology and new forms of theorizing. To this aim, we develop a speculative political ecological approach grounded on a numerical model that examines the potential of transformative change in the aftermath of extreme flood events in a capitalist city. Analytically, this opens a unique possibility of exploring urban futures beyond current trajectories, and how these alternative futures might transform vulnerability and inequality across urban spaces. From a policy perspective, we lay the foundations for a new generation of models that apprehend the role of power and agency in shaping uneven urban futures of climate extremes.

Seuils de précipitation, variabilité spatiotemporelle et tendances climatiques des pluies torrentielles en Haute-Gaspésie, Québec. Comptes rendus de la 8e conférence canadienne sur la géotechnique et les risques naturels (Géorisques 8), La Société canadienne de géotechnique, Québec. - Boulet, Y.; Gauthier, F.; Buffin-Bélanger, T.; Hétu, B. (2022)

International Guidelines on Natural and Nature-Based Features - Bridges, Todd; Simm, Jonathan; King, Jeffrey (Science and practice for an uncertain future, 2021)

Mers montantes et sables mouvants : Allier les infrastructures naturelles et grises pour protéger les collectivités côtières. - Eyquem, Joanna (2021)
Keywords: Ouvrage_Collectif_Numéro1

Earthquake Fatalities: The Interaction of Nature and Political Economy - Anbarci, Nejat; Escaleras, Monica; Register, Charles A. (Journal of Public Economics, 2005)
MAG ID: 2117200072

Understanding Uncertainty in Probabilistic Floodplain Mapping in the Time of Climate Change - Zahmatkesh, Zahra; Han, Shasha; Coulibaly, Paulin (Water, 2021)
An integrated framework was employed to develop probabilistic floodplain maps, taking into account hydrologic and hydraulic uncertainties under climate change impacts. To develop the maps, several scenarios representing the individual and compounding effects of the models’ input and parameters uncertainty were defined. Hydrologic model calibration and validation were performed using a Dynamically Dimensioned Search algorithm. A generalized likelihood uncertainty estimation method was used for quantifying uncertainty. To draw on the potential benefits of the proposed methodology, a flash-flood-prone urban watershed in the Greater Toronto Area, Canada, was selected. The developed floodplain maps were updated considering climate change impacts on the input uncertainty with rainfall Intensity–Duration–Frequency (IDF) projections of RCP8.5. The results indicated that the hydrologic model input poses the most uncertainty to floodplain delineation. Incorporating climate change impacts resulted in the expansion of the potential flood area and an increase in water depth. Comparison between stationary and non-stationary IDFs showed that the flood probability is higher when a non-stationary approach is used. The large inevitable uncertainty associated with floodplain mapping and increased future flood risk under climate change imply a great need for enhanced flood modeling techniques and tools. The probabilistic floodplain maps are beneficial for implementing risk management strategies and land-use planning.

Disaster risk, climate change, and poverty: assessing the global exposure of poor people to floods and droughts - Winsemius, Hessel C.; Jongman, Brenden; Veldkamp, Ted I.E.; Hallegatte, Stephane; Bangalore, Mook; Ward, Philip J. (Environment and Development Economics, 2018)
Abstract People living in poverty are particularly vulnerable to shocks, including those caused by natural disasters such as floods and droughts. This paper analyses household survey data and hydrological riverine flood and drought data for 52 countries to find out whether poor people are disproportionally exposed to floods and droughts, and how this exposure may change in a future climate. We find that poor people are often disproportionally exposed to droughts and floods, particularly in urban areas. This pattern does not change significantly under future climate scenarios, although the absolute number of people potentially exposed to floods or droughts can increase or decrease significantly, depending on the scenario and region. In particular, many countries in Africa show a disproportionally high exposure of poor people to floods and droughts. For these hotspots, implementing risk-sensitive land-use and development policies that protect poor people should be a priority.

River flood plains are model ecosystems to test general hydrogeomorphic and ecological concepts - Tockner, Klement; Lorang, Mark S.; Stanford, Jack A. (River Research and Applications, 2010)
Abstract A major challenge in ecology is to link patterns and processes across different spatial and temporal scales. Flood plains are ideal model ecosystems to study (i) the processes that create and maintain environmental heterogeneity and (ii) to quantify the effects of environmental heterogeneity on ecosystem functioning and biodiversity. Fluvial processes of cut‐and‐fill alluviation create new channels, bars and benches within a flood plain that in turn provides new surface for subsequent vegetative recruitment and growth resulting in a shifting mosaic of interconnected aquatic and terrestrial habitat patches. Composition and spatial arrangement of these habitat patches control the movement of organisms and matter among adjacent patches; and the capacity of a habitat to process matter depends on the productivity of adjacent patches and on the exchange among these patches. The exchange of matter and organisms among habitats of different age and productivity is often pulsed in nature. Small pulses of a physical driver (e.g. short‐term increase in flow) can leach large amounts of nutrients thereby stimulating primary production in adjacent aquatic patches, or trigger mass emergence of aquatic insects that may in turn impact recipient terrestrial communities. Hence, biodiversity in a river corridor context is hierarchically structured and strongly linked to the dynamic biophysical processes and feedback mechanisms that drive these chronosequences over broad time and space scales. Today, the active conversion of degraded ecosystems back to a more heterogeneous and dynamic state has become an important aspect of restoration and management where maintaining or allowing a return to the shifting habitat mosaic dynamism is the goal with the expected outcome greater biodiversity and clean water among other valuable ecosystem goods and services. Copyright © 2009 John Wiley & Sons, Ltd.
Keywords: Ouvrage_Collectif_Numéro1

The impact of flooding on aquatic ecosystem services - Talbot, Ceara J.; Bennett, Elena M.; Cassell, Kelsie; Hanes, Daniel M.; Minor, Elizabeth C.; Paerl, Hans; Raymond, Peter A.; Vargas, Rodrigo; Vidon, Philippe G.; Wollheim, Wilfred; Xenopoulos, Marguerite A. (Biogeochemistry, 2018)

Integrating climate change induced flood risk into future population projections - Shu, Evelyn G.; Porter, Jeremy R.; Hauer, Mathew E.; Sandoval Olascoaga, Sebastian; Gourevitch, Jesse; Wilson, Bradley; Pope, Mariah; Melecio-Vazquez, David; Kearns, Edward (Nature Communications, 2023)
Abstract Flood exposure has been linked to shifts in population sizes and composition. Traditionally, these changes have been observed at a local level providing insight to local dynamics but not general trends, or at a coarse resolution that does not capture localized shifts. Using historic flood data between 2000-2023 across the Contiguous United States (CONUS), we identify the relationships between flood exposure and population change. We demonstrate that observed declines in population are statistically associated with higher levels of historic flood exposure, which may be subsequently coupled with future population projections. Several locations have already begun to see population responses to observed flood exposure and are forecasted to have decreased future growth rates as a result. Finally, we find that exposure to high frequency flooding (5 and 20-year return periods) results in 2-7% lower growth rates than baseline projections. This is exacerbated in areas with relatively high exposure to frequent flooding where growth is expected to decline over the next 30 years.

Assessing the impact of climate change on the frequency of floods in the Red River basin - Rasmussen, Peter F. (2016)
The impact of climate change on the frequency distribution of spring floods in the Red River basin is investigated. Several major floods in the last couple of decades have caused major damages and inconvenience to people living in the Red River flood plain south of Winnipeg, and have raised the question of whether climate change is at least partly responsible for what appears to be more frequent occurrences of high spring runoff. To investigate whether this is the case, a regression model is used to associate spring peak flow at the US–Canada border with predictor variables that include antecedent precipitation in the previous fall (used as a proxy for soil moisture at freeze-up), winter snow accumulation and spring precipitation. Data from the Coupled Model Intercomparison Project – Phase 5 (CMIP5) are used to derive information about possible changes to the predictor variables in the future, and this information is then used to derive flood distributions for future climate conditions. While mean monthly...
MAG ID: 964228376

Flood Risk Assessment under Climate Change: The Petite Nation River Watershed - Oubennaceur, Khalid; Chokmani, Karem; Gauthier, Yves; Ratte-Fortin, Claudie; Homayouni, Saeid; Toussaint, Jean-Patrick (Climate, 2021)
In Canada, climate change is expected to increase the extreme precipitation events by magnitude and frequency, leading to more intense and frequent river flooding. In this study, we attempt to map the flood hazard and damage under projected climate scenarios (2050 and 2080). The study was performed in the two most populated municipalities of the Petite Nation River Watershed, located in southern Quebec (Canada). The methodology follows a modelling approach, in which climate projections are derived from the Hydroclimatic Atlas of Southern Quebec following two representative concentration pathways (RCPs) scenarios, i.e., RCP 4.5 and RCP 8.5. These projections are used to predict future river flows. A frequency analysis was carried out with historical data of the peak flow (period 1969–2018) to derive different return periods (2, 20, and 100 years), which were then fed into the GARI tool (Gestion et Analyse du Risque d’Inondation). This tool is used to simulate flood hazard maps and to quantify future flood risk changes. Projected flood hazard (extent and depth) and damage maps were produced for the two municipalities under current and for future scenarios. The results indicate that the flood frequencies are expected to show a minor decrease in peak flows in the basin at the time horizons, 2050 and 2080. In addition, the depth and inundation areas will not significantly change for two time horizons, but instead show a minor decrease. Similarly, the projected flood damage changes in monetary losses are projected to decrease in the future. The results of this study allow one to identify present and future flood hazards and vulnerabilities, and should help decision-makers and the public to better understand the significance of climate change on flood risk in the Petite Nation River watershed.
Keywords: Site_internet_RIISQ

Flood risk and adaptation strategies under climate change and urban expansion: A probabilistic analysis using global data. - Muis, Sanne; Güneralp, Burak; Jongman, Brenden; Aerts, Jeroen C. J. H.; Ward, Philip B.; Ward, Philip J. (Science of The Total Environment, 2015)
MAG ID: 1190333981

Floodplains in the Anthropocene: A Global Analysis of the Interplay Between Human Population, Built Environment, and Flood Severity - Mazzoleni, M.; Mård, J.; Rusca, M.; Odongo, V.; Lindersson, S.; Di Baldassarre, G. (Water Resources Research, 2021)
Abstract This study presents a global explanatory analysis of the interplay between the severity of flood losses and human presence in floodplain areas. In particular, we relate economic losses and fatalities caused by floods during 1990–2000, with changes in human population and built‐up areas in floodplains during 2000–2015 by exploiting global archives. We found that population and built‐up areas in floodplains increased in the period 2000–2015 for the majority of the analyzed countries, albeit frequent flood losses in the previous period 1990–2000. In some countries, however, population in floodplains decreased in the period 2000–2015, following more severe floods losses that occurred in the period 1975–2000. Our analysis shows that (i) in low‐income countries, population in floodplains increased after a period of high flood fatalities; while (ii) in upper‐middle and high‐income countries, built‐up areas increased after a period of frequent economic losses. In this study, we also provide a general framework to advance knowledge of human‐flood interactions and support the development of sustainable policies and measures for flood risk management and disaster risk reduction. , Key Points We analyzed the interplay between the severity of flood losses and human presence in floodplains using freely available global data sets Despite the frequent flood losses in the period 1990–2000, human presence and built‐up areas in the floodplains increased between 2000 and 2015 In low‐income countries, population in floodplains increased after a period of high flood fatalities

Multi-Scale Flood Mapping under Climate Change Scenarios in Hexagonal Discrete Global Grids - Li, Mingke; McGrath, Heather; Stefanakis, Emmanuel (ISPRS International Journal of Geo-Information, 2022)
Among the most prevalent natural hazards, flooding has been threatening human lives and properties. Robust flood simulation is required for effective response and prevention. Machine learning is widely used in flood modeling due to its high performance and scalability. Nonetheless, data pre-processing of heterogeneous sources can be cumbersome, and traditional data processing and modeling have been limited to a single resolution. This study employed an Icosahedral Snyder Equal Area Aperture 3 Hexagonal Discrete Global Grid System (ISEA3H DGGS) as a scalable, standard spatial framework for computation, integration, and analysis of multi-source geospatial data. We managed to incorporate external machine learning algorithms with a DGGS-based data framework, and project future flood risks under multiple climate change scenarios for southern New Brunswick, Canada. A total of 32 explanatory factors including topographical, hydrological, geomorphic, meteorological, and anthropogenic were investigated. Results showed that low elevation and proximity to permanent waterbodies were primary factors of flooding events, and rising spring temperatures can increase flood risk. Flooding extent was predicted to occupy 135–203% of the 2019 flood area, one of the most recent major flooding events, by the year 2100. Our results assisted in understanding the potential impact of climate change on flood risk, and indicated the feasibility of DGGS as the standard data fabric for heterogeneous data integration and incorporated in multi-scale data mining.

Sensitivity of modern and Holocene floods to climate change - Knox, James C. (Quaternary Science Reviews, 2000)
Keywords: Ouvrage_Collectif_Numéro1

Impacts of climate change on flood volumes over North American catchments - Ionno, Alexandre; Arsenault, Richard; Troin, Magali; Martel, Jean-Luc; Brissette, François (Journal of Hydrology, 2024)

Flooding Related Consequences of Climate Change on Canadian Cities and Flow Regulation Infrastructure - Gaur, Ayushi; Gaur, Abhishek; Yamazaki, Dai; Simonovic, Slobodan P. (Water, 2019)
This study discusses the flooding related consequences of climate change on most populous Canadian cities and flow regulation infrastructure (FRI). The discussion is based on the aggregated results of historical and projected future flooding frequencies and flood timing as generated by Canada-wide hydrodynamic modelling in a previous study. Impact assessment on 100 most populous Canadian cities indicate that future flooding frequencies in some of the most populous cities such as Toronto and Montreal can be expected to increase from 100 (250) years to 15 (22) years by the end of the 21st century making these cities highest at risk to projected changes in flooding frequencies as a consequence of climate change. Overall 40–60% of the analyzed cities are found to be associated with future increases in flooding frequencies and associated increases in flood hazard and flood risk. The flooding related impacts of climate change on 1072 FRIs located across Canada are assessed both in terms of projected changes in future flooding frequencies and changes in flood timings. Results suggest that 40–50% of the FRIs especially those located in southern Ontario, western coastal regions, and northern regions of Canada can be expected to experience future increases in flooding frequencies. FRIs located in many of these regions are also projected to experience future changes in flood timing underlining that operating rules for those FRIs may need to be reassessed to make them resilient to changing climate.
MAG ID: 2908236810

Environmental injustice and flood risk: a conceptual model and case comparison of metropolitan Miami and Houston, USA - Collins, Timothy W.; Grineski, Sara E.; Chakraborty, Jayajit (Regional Environmental Change, 2018)

Exploring the Environmental Justice Implications of Hurricane Harvey Flooding in Greater Houston, Texas. - Chakraborty, Jayajit; Collins, Timothy W.; Grineski, Sara E. (American Journal of Public Health, 2019)
Objectives. To assess the environmental justice implications of flooding from Hurricane Harvey in Greater Houston, Texas, we analyzed whether the areal extent of flooding was distributed inequitably with respect to race, ethnicity, and socioeconomic status, after controlling for relevant explanatory factors.Methods. Our study integrated cartographic information from Harvey’s Inundation Footprint, developed by the US Federal Emergency Management Agency, with sociodemographic data from the 2012–2016 American Community Survey. Statistical analyses were based on bivariate correlations and multivariate generalized estimating equations.Results. The areal extent of Harvey-induced flooding was significantly greater in neighborhoods with a higher proportion of non-Hispanic Black and socioeconomically deprived residents after we controlled for contextual factors and clustering.Conclusions. Results provide evidence of racial/ethnic and socioeconomic injustices in the distribution of flooding and represent an importa...
MAG ID: 2906468836

At what scales do climate variability and land cover change impact on flooding and low flows? - Blöschl, Günter; Ardoin-Bardin, Sandra; Bonell, Mike; Dorninger, Manfred; Goodrich, David; Gutknecht, Dieter; Matamoros, David; Merz, Bruno; Shand, Paul; Szolgay, Jan (Hydrological Processes, 2007)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/hyp.6669
Keywords: Ouvrage_Collectif_Numéro1

Changements climatiques : le niveau de préparation des provinces et territoires canadiens aux risques d’inondations - Feltmate, Blair; Moudrak, Marina; Bakos, Kathryn (Centre Intact d’adaptation au climat, Université de Waterloo, 2020)
Keywords: Ouvrage_Collectif_Numéro1

Être jeune et exposé à un désastre technologique : le vécu des jeunes de la communauté de Lac-Mégantic - Maltais, Danielle; Pouliot, Ève; Petit, G. (2018)
A la suite de la tragedie ferroviaire de Lac-Megantic de 2013, des enquetes populationnelles ont permis de dresser un portrait de la sante des adultes vivant sur le territoire de la MRC du Granit, sans toutefois repertorier le vecu specifique des jeunes. Le present document vise a combler cette lacune en offrant un bilan de la realite et des besoins des jeunes âges de 10 a 25 ans demeurant au sein de la communaute de Lac-Megantic. Il presente les resultats d'une etude mixte realisee a l'hiver 2017 aupres d'eleves de second cycle de quatre ecoles primaires (5e et 6e annees), de la polyvalente Montignac, ainsi que d'etudiants frequentant le Centre de formation professionnelle Le Granit, le centre d'etudes collegiales de Lac-Megantic et le Centre d'education des adultes de la Commission scolaire des Hauts-Cantons, secteur Lac-Megantic. Cet ouvrage s'adresse aux chercheurs, aux etudiants ainsi qu'aux professionnels des milieux scolaires et du reseau de la sante et des services sociaux qui s'interessent au vecu des jeunes a la suite d'une catastrophe. Plus precisement, il permet de mieux connaitre les caracteristiques personnelles, familiales, scolaires et sociales des jeunes de la commmunaute de Lac-Megantic, tout en leur donnant la parole sur leurs attentes, leurs desirs et leurs besoins.
Keywords: Ouvrage_Collectif_Numéro1

Predicting malaria risk considering vector control interventions under climate change scenarios - Sadoine, Margaux L.; Zinszer, Kate; Liu, Ying; Gachon, Philippe; Fournier, Michel; Dueymes, Guillaume; Dorsey, Grant; Llerena, Ana; Namuganga, Jane Frances; Nasri, Bouchra; Smargiassi, Audrey (Scientific Reports, 2024)
Many studies have projected malaria risks with climate change scenarios by modelling one or two environmental variables and without the consideration of malaria control interventions. We aimed to predict the risk of malaria with climate change considering the influence of rainfall, humidity, temperatures, vegetation, and vector control interventions (indoor residual spraying (IRS) and long-lasting insecticidal nets (LLIN)). We used negative binomial models based on weekly malaria data from six facility-based surveillance sites in Uganda from 2010–2018, to estimate associations between malaria, environmental variables and interventions, accounting for the non-linearity of environmental variables. Associations were applied to future climate scenarios to predict malaria distribution using an ensemble of Regional Climate Models under two Representative Concentration Pathways (RCP4.5 and RCP8.5). Predictions including interaction effects between environmental variables and interventions were also explored. The results showed upward trends in the annual malaria cases by 25% to 30% by 2050s in the absence of intervention but there was great variability in the predictions (historical vs RCP 4.5 medians [Min–Max]: 16,785 [9,902–74,382] vs 21,289 [11,796–70,606]). The combination of IRS and LLIN, IRS alone, and LLIN alone would contribute to reducing the malaria burden by 76%, 63% and 35% respectively. Similar conclusions were drawn from the predictions of the models with and without interactions between environmental factors and interventions, suggesting that the interactions have no added value for the predictions. The results highlight the need for maintaining vector control interventions for malaria prevention and control in the context of climate change given the potential public health and economic implications of increasing malaria in Uganda.
Keywords: Gachon_Philippe

Differential Influence of Environmental Factors on Malaria Due to Vector Control Interventions in Uganda - Sadoine, Margaux L.; Smargiassi, Audrey; Liu, Ying; Gachon, Philippe; Fournier, Michel; Dueymes, Guillaume; Namuganga, Jane Frances; Dorsey, Grant; Nasri, Bouchra; Zinszer, Kate (International Journal of Environmental Research and Public Health, 2023)
Background: Few studies have explored how vector control interventions may modify associations between environmental factors and malaria. Methods: We used weekly malaria cases reported from six public health facilities in Uganda. Environmental variables (temperature, rainfall, humidity, and vegetation) were extracted from remote sensing sources. The non-linearity of environmental variables was investigated, and negative binomial regression models were used to explore the influence of indoor residual spraying (IRS) and long-lasting insecticidal nets (LLINs) on associations between environmental factors and malaria incident cases for each site as well as pooled across the facilities, with or without considering the interaction between environmental variables and vector control interventions. Results: An average of 73.3 weekly malaria cases per site (range: 0–597) occurred between 2010 and 2018. From the pooled model, malaria risk related to environmental variables was reduced by about 35% with LLINs and 63% with IRS. Significant interactions were observed between some environmental variables and vector control interventions. There was site-specific variability in the shape of the environment–malaria risk relationship and in the influence of interventions (6 to 72% reduction in cases with LLINs and 43 to 74% with IRS). Conclusion: The influence of vector control interventions on the malaria–environment relationship need to be considered at a local scale in order to efficiently guide control programs.
Keywords: Gachon_Philippe

Differential impact of environment on malaria due to control interventions in Uganda, 2010-2018 - Sadoine, Margaux; Smargiassi, Audrey; Liu, Ying; Gachon, Philippe; Dueymes, Guillaume; Namuganga, Jane Frances; Dorsey, Grant; Fournier, Michel; Nasri, Bouchra; Zinszer, Kate (ISEE Conference Abstracts, 2022)
Keywords: Gachon_Philippe

The influence of the environment and indoor residual spraying on malaria risk in a cohort of children in Uganda - Sadoine, Margaux L.; Smargiassi, Audrey; Liu, Ying; Gachon, Philippe; Dueymes, Guillaume; Dorsey, Grant; Fournier, Michel; Nankabirwa, Joaniter I.; Rek, John; Zinszer, Kate (Scientific Reports, 2022)
Studies have estimated the impact of the environment on malaria incidence although few have explored the differential impact due to malaria control interventions. Therefore, the objective of the study was to evaluate the effect of indoor residual spraying (IRS) on the relationship between malaria and environment (i.e. rainfall, temperatures, humidity, and vegetation) using data from a dynamic cohort of children from three sub-counties in Uganda. Environmental variables were extracted from remote sensing sources and averaged over different time periods. General linear mixed models were constructed for each sub-counties based on a log-binomial distribution. The influence of IRS was analysed by comparing marginal effects of environment in models adjusted and unadjusted for IRS. Great regional variability in the shape (linear and non-linear), direction, and magnitude of environmental associations with malaria risk were observed between sub-counties. IRS was significantly associated with malaria risk reduction (risk ratios vary from RR = 0.03, CI 95% [0.03–0.08] to RR = 0.35, CI95% [0.28–0.42]). Model adjustment for this intervention changed the magnitude and/or direction of environment-malaria associations, suggesting an interaction effect. This study evaluated the potential influence of IRS in the malaria-environment association and highlighted the necessity to control for interventions when they are performed to properly estimate the environmental influence on malaria. Local models are more informative to guide intervention program compared to national models.
Keywords: Gachon_Philippe

Climate change alone cannot explain boreal caribou range recession in Quebec since 1850 - Morineau, Chloé; Boulanger, Yan; Gachon, Philippe; Plante, Sabrina; St‐Laurent, Martin‐Hugues (Global Change Biology, 2023)
Abstract The contraction of species range is one of the most significant symptoms of biodiversity loss worldwide. While anthropogenic activities and habitat alteration are major threats for several species, climate change should also be considered. For species at risk, differentiating the effects of human disturbances and climate change on past and current range transformations is an important step towards improved conservation strategies. We paired historical range maps with global atmospheric reanalyses from different sources to assess the potential effects of recent climate change on the observed northward contraction of the range of boreal populations of woodland caribou ( Rangifer tarandus caribou ) in Quebec (Canada) since 1850. We quantified these effects by highlighting the discrepancies between different southern limits of the caribou's range (used as references) observed in the past and reconstitutions obtained through the hindcasting of the climate conditions within which caribou are currently found. Hindcasted southern limits moved ~105 km north over time under all reanalysis datasets, a trend drastically different from the ~620 km reported for observed southern limits since 1850. The differences in latitudinal shift through time between the observed and hindcasted southern limits of distribution suggest that caribou range recession should have been only 17% of what has been observed since 1850 if recent climate change had been the only disturbance driver. This relatively limited impact of climate reinforces the scientific consensus stating that caribou range recession in Quebec is mainly caused by anthropogenic drivers (i.e. logging, development of the road network, agriculture, urbanization) that have modified the structure and composition of the forest over the past 160 years, paving the way for habitat‐mediated apparent competition and overharvesting. Our results also call for a reconsideration of past ranges in models aiming at projecting future distributions, especially for endangered species.
Keywords: Gachon_Philippe

Risk assessment strategies for early detection and prediction of infectious disease outbreaks associated with climate change - Rees, Ee; Ng, V; Gachon, P; Mawudeku, A; McKenney, D; Pedlar, J; Yemshanov, D; Parmely, J; Knox, J (Canada Communicable Disease Report, 2019)
Keywords: Gachon_Philippe

Stratégie d’évaluation des risques servant à la détection précoce et à la prédiction des éclosions de maladies infectieuses associées aux changements climatiques - Rees, Ee; Ng, V; Gachon, P; Mawudeku, A; McKenney, D; Pedlar, J; Yemshanov, D; Parmely, J; Knox, J (Relevé des maladies transmissibles au Canada, 2019)
Keywords: Gachon_Philippe

Climate change and infectious diseases: What can we expect? - Ogden, Nh; Gachon, P (Canada Communicable Disease Report, 2019)
Keywords: Gachon_Philippe

Which downscaled rainfall data for climate change impact studies in urban areas? Review of current approaches and trends - Gooré Bi, Eustache; Gachon, Philippe; Vrac, Mathieu; Monette, Frédéric (Theoretical and Applied Climatology, 2017)
Changes in extreme precipitation should be one of the primary impacts of climate change (CC) in urban areas. To assess these impacts, rainfall data from climate models are commonly used. The main goal of this paper is to report on the state of knowledge and recent works on the study of CC impacts with a focus on urban areas, in order to produce an integrated review of various approaches to which future studies can then be compared or constructed. Model output statistics (MOS) methods are increasingly used in the literature to study the impacts of CC in urban settings. A review of previous works highlights the non-stationarity nature of future climate data, underscoring the need to revise urban drainage system design criteria. A comparison of these studies is made difficult, however, by the numerous sources of uncertainty arising from a plethora of assumptions, scenarios, and modeling options. All the methods used do, however, predict increased extreme precipitation in the future, suggesting potential risks of combined sewer overflow frequencies, flooding, and back-up in existing sewer systems in urban areas. Future studies must quantify more accurately the different sources of uncertainty by improving downscaling and correction methods. New research is necessary to improve the data validation process, an aspect that is seldom reported in the literature. Finally, the potential application of non-stationarity conditions into generalized extreme value (GEV) distribution should be assessed more closely, which will require close collaboration between engineers, hydrologists, statisticians, and climatologists, thus contributing to the ongoing reflection on this issue of social concern.
Keywords: Gachon_Philippe

Quantitative and qualitative assessment of the impact of climate change on a combined sewer overflow and its receiving water body - Gooré Bi, Eustache; Monette, Frédéric; Gachon, Philippe; Gaspéri, Johnny; Perrodin, Yves (Environmental Science and Pollution Research, 2015)
Projections from the Canadian Regional Climate Model (CRCM) for the southern part of the province of Québec, Canada, suggest an increase in extreme precipitation events for the 2050 horizon (2041–2070). The main goal of this study consisted in a quantitative and qualitative assessment of the impact of the 20 % increase in rainfall intensity that led, in the summer of 2013, to overflows in the “Rolland-Therrien” combined sewer system in the city of Longueuil, Canada. The PCSWMM 2013 model was used to assess the sensitivity of this overflow under current (2013) and future (2050) climate conditions. The simulated quantitative variables (peak flow, QCSO, and volume discharged, VD) served as the basis for deriving ecotoxicological risk indices and event fluxes (EFs) transported to the St. Lawrence (SL) River. Results highlighted 15 to 500 % increases in VD and 13 to 148 % increases in QCSO by 2050 (compared to 2013), based on eight rainfall events measured from May to October. These results show that (i) the relationships between precipitation and combined sewer overflow variables are not linear and (ii) the design criteria for current hydraulic infrastructure must be revised to account for the impact of climate change (CC) arising from changes in precipitation regimes. EFs discharged into the SL River will be 2.24 times larger in the future than they are now (2013) due to large VDs resulting from CC. This will, in turn, lead to excessive inputs of total suspended solids (TSSs) and tracers for numerous urban pollutants (organic matter and nutrients, metals) into the receiving water body. Ecotoxicological risk indices will increase by more than 100 % by 2050 compared to 2013. Given that substantial VDs are at play, and although CC scenarios have many sources of uncertainty, strategies to adapt this drainage network to the effects of CC will have to be developed.
Keywords: Gachon_Philippe

Large Scale Flood Risk Mapping in Data Scarce Environments: An Application for Romania - Albano, Raffaele; Samela, Caterina; Crăciun, Iulia; Manfreda, Salvatore; Adamowski, Jan; Sole, Aurelia; Sivertun, Åke; Ozunu, Alexandru (Water, 2020)
Large-scale flood risk assessment is essential in supporting national and global policies, emergency operations and land-use management. The present study proposes a cost-efficient method for the large-scale mapping of direct economic flood damage in data-scarce environments. The proposed framework consists of three main stages: (i) deriving a water depth map through a geomorphic method based on a supervised linear binary classification; (ii) generating an exposure land-use map developed from multi-spectral Landsat 8 satellite images using a machine-learning classification algorithm; and (iii) performing a flood damage assessment using a GIS tool, based on the vulnerability (depth–damage) curves method. The proposed integrated method was applied over the entire country of Romania (including minor order basins) for a 100-year return time at 30-m resolution. The results showed how the description of flood risk may especially benefit from the ability of the proposed cost-efficient model to carry out large-scale analyses in data-scarce environments. This approach may help in performing and updating risk assessments and management, taking into account the temporal and spatial changes in hazard, exposure, and vulnerability.

Climate indices to characterize climatic changes across southern Canada - Wazneh, Hussein; Arain, M. Altaf; Coulibaly, Paulin (Meteorological Applications, 2020)
Abstract The present study analyses the impacts of past and future climate change on extreme weather events for southern parts of Canada from 1981 to 2100. A set of precipitation and temperature‐based indices were computed using the downscaled Coupled Model Intercomparison Project Phase 5 (CMIP5) multi‐model ensemble projections at 8 km resolution over the 21st Century for two representative concentration pathway (RCP) scenarios: RCP4.5 and RCP8.5. The results show that this region is expected to experience stronger warming and a higher increase in precipitation extremes in future. Generally, projected changes in minimum temperature will be greater than changes in maximum temperature, as shown by respective indices. A decrease in frost days and an increase in warm nights will be expected. By 2100 there will be no cool nights and cool days. Daily minimum and maximum temperatures will increase by 12 and 7°C, respectively, under the RCP8.5 scenario, when compared with the reference period 1981–2000. The highest warming in minimum temperature and decrease in cool nights and days will occur in Ontario and Quebec provinces close to the Great Lakes and Hudson Bay. The highest warming in maximum temperature will occur in the southern parts of Alberta and Saskatchewan. Annual total precipitation is expected to increase by about 16% and the occurrence of heavy precipitation events by five days. The highest increase in annual total precipitation will occur in the northern parts of Ontario and Quebec and in western British Columbia.

Individual and environmental correlates of tap water consumption among adolescents in Canada - Vézina-Im, Lydi-Anne; Beaulieu, Dominique; Turcotte, Stéphane; Turcotte, Anne-Frédérique; Lessard, Lily; Delisle-Martel, Joannie; Boucher, Danielle; Labbé, Valérie; Gingras, Mariane (Appetite, 2024)
Keywords: Lessard_Lily

Changes in Canada's Climate: Trends in Indices Based on Daily Temperature and Precipitation Data - Vincent, L.A.; Zhang, Xuebin; Mekis, É.; Wan, Hui; Bush, E.J. (Atmosphere-ocean, 2018)
ABSTRACTTrends in indices based on daily temperature and precipitation are examined for two periods: 1948–2016 for all stations in Canada and 1900–2016 for stations in the south of Canada. These in...
MAG ID: 2898176169

Assessment of the Potential Hydrological Impacts of Climate Change in Quebec—Canada, a Refined Neutral Approach - Valencia Giraldo, Marinela Del Carmen; Ricard, Simon; Anctil, François (Water, 2023)
There is currently much discussion as to whether probabilistic (top–down) or possibilistic (bottom–up) approaches are the most appropriate to estimate potential future climate impacts. In a context of deep uncertainty, such as future climate, bottom-up approaches aimed at assessing the sensitivity and vulnerability of systems to changes in climate variables have been gaining ground. A refined framework is proposed here (in terms of coherence, structure, uncertainty, and results analysis) that adopts the scenario–neutral method of the bottom–up approach, but also draws on some elements of the top–down approach. What better guides the task of assessing the potential hydroclimatological impacts of changing climatic conditions in terms of the sensitivity of the systems, differential analysis of climatic stressors, paths of change, and categorized response of the scenarios: past, changing, compensatory, and critical condition. The results revealed a regional behavior (of hydroclimatology, annual water balances, and snow) and a differential behavior (of low flows). We find, among others, the plausible scenario in which increases in temperature and precipitation would generate the same current mean annual flows, with a reduction of half of the snow, a decrease in low flows (significant, but differentiated between basins), and a generalized increase in dry events.

Potential impact of climate change on the risk of windthrow in eastern Canada’s forests - Saad, Christian; Boulanger, Yan; Beaudet, Marilou; Gachon, Philippe; Ruel, Jean-Claude; Gauthier, Sylvie (Climatic Change, 2017)
Climate change is likely to affect windthrow risks at northern latitudes by potentially changing high wind probabilities and soil frost duration. Here, we evaluated the effect of climate change on windthrow risk in eastern Canada’s balsam fir (Abies balsamea [L.] Mill.) forests using a methodology that accounted for changes in both wind speed and soil frost duration. We used wind speed and soil temperature projections at the regional scale from the CRCM5 regional climate model (RCM) driven by the CanESM2 global climate model (GCM) under two representative concentration pathways (RCP4.5, RCP8.5), for a baseline (1976–2005) and two future periods (2041–2070, 2071–2100). A hybrid mechanistic model (ForestGALES) that considers species resistance to uprooting and wind speed distribution was used to calculate windthrow risk. An increased risk of windthrow (3 to 30%) was predicted for the future mainly due to an increased duration of unfrozen soil conditions (by up to 2 to 3 months by the end of the twenty-first century under RCP8.5). In contrast, wind speed did not vary markedly with a changing climate. Strong regional variations in wind speeds translated into regional differences in windthrow risk, with the easternmost region (Atlantic provinces) having the strongest winds and the highest windthrow risk. Because of the inherent uncertainties associated with climate change projections, especially regarding wind climate, further research is required to assess windthrow risk from the optimum combination of RCM/GCM ensemble simulations.
Keywords: Gachon_Philippe

Participatory mapping of ecosystem services to understand stakeholders’ perceptions of the future of the Mactaquac Dam, Canada - Reilly, Kate; Adamowski, Jan; John, Kimberly (Ecosystem Services, 2018)

Assessment of the Probability of Autochthonous Transmission of Chikungunya Virus in Canada under Recent and Projected Climate Change - Ng, Victoria; Fazil, Aamir; Gachon, Philippe; Deuymes, Guillaume; Radojević, Milka; Mascarenhas, Mariola; Garasia, Sophiya; Johansson, Michael A.; Ogden, Nicholas H. (Environmental Health Perspectives, 2017)
Keywords: Gachon_Philippe

Changes in floodplain regimes over Canada due to climate change impacts: Observations from CMIP6 models - Mohanty, Mohit Prakash; Simonovic, Slobodan P. (Science of The Total Environment, 2021)
Abstract With the recent Coupled Model Intercomparison Project Phase 6 (CMIP6), water experts and flood modellers are curious to explore the efficacy of the new and upgraded climate models in representing flood inundation dynamics and how they will be impacted in the future by climate change. In this study, for the first time, we consider the latest group of General Circulation Models (GCMs) from CMIP6 to examine the probable changes in floodplain regimes over Canada. A set of 17 GCMs from Shared Socioeconomic Pathways (SSPs) 4.5 (medium forcing) and 8.5 (high end forcing) common to historical (1980 to 2019), near-future (2021 to 2060), and far-future (2061 to 2100) time-periods are selected. A comprehensive framework consisting of hydrodynamic flood modelling, and statistical experiments are put forward to derive high-resolution Canada-wide floodplain maps for 100 and 200-yr return periods. The changes in floodplain regimes for the future periods are analyzed over drainage basin scale in terms of (i) changes in flood inundation extents, (ii) changes in flood hazards (high and very-high classes), and (iii) changes in flood frequency. Our results show a significant rise (>30%) in flood inundation extents in the future periods; particularly intense over western and eastern regions. The flood hazards are expected to cover ~16% more geographical area of Canada. We also find that large areas in northern and western Canada and a few spots in the eastern parts of Canada will be getting flooded more frequently compared to the historical period. The observations derived from this study are vital for enhancing flood preparedness, optimal land-use planning, and refurbishing both structural and non-structural flood control options for improved resilience. The study instills new knowledge on revamping the existing flood management approaches and adaptation strategies for future protection.
MAG ID: 3166747757

Modelling the impacts of climate change on riverine thermal regimes in western Canada's largest Pacific watershed. - Islam, Siraj ul; Hay, Rachel W.; Déry, Stephen J.; Booth, Barry P. (Scientific Reports, 2019)
Quantification of climate change impacts on the thermal regimes of rivers in British Columbia (BC) is crucial given their importance to aquatic ecosystems. Using the Air2Stream model, we investigate the impact of both air temperature and streamflow changes on river water temperatures from 1950 to 2015 across BC’s 234,000 km2 Fraser River Basin (FRB). Model results show the FRB’s summer water temperatures rose by nearly 1.0°C during 1950–2015 with 0.47°C spread across 17 river sites. For most of these sites, such increases in average summer water temperature have doubled the number of days exceeding 20°C, the water temperature that, if exceeded, potentially increases the physiological stress of salmon during migration. Furthermore, river sites, especially those in the upper and middle FRB, show significant associations between Pacific Ocean teleconnections and regional water temperatures. A multivariate linear regression analysis reveals that air temperature primarily controls simulated water temperatures in the FRB by capturing ~80% of its explained variance with secondary impacts through river discharge. Given such increases in river water temperature, salmon returning to spawn inthe Fraser River and its tributaries are facing continued and increasing physical challenges now and potentially into the future.
MAG ID: 2964716869

Projected seasonal flooding in Canada under climate change with statistical and machine learning - Grenier, Manuel; Boudreault, Jérémie; Raymond, Sébastien; Boudreault, Mathieu (Journal of Hydrology: Regional Studies, 2024)
Keywords: Infolettre; Infolettre_Mai_2024

Modelling of future flood risk across Canada due to climate change - Gaur, Ayushi; Gaur, Abhishek; Simonovic, Slobodan P. (2018)

Impacts of Model Bias on the Climate Change Signal and Effects of Weighted Ensembles of Regional Climate Model Simulations: A Case Study over Southern Québec, Canada - Eum, Hyung-Il; Gachon, Philippe; Laprise, René (Advances in Meteorology, 2016)
This study examined the impact of model biases on climate change signals for daily precipitation and for minimum and maximum temperatures. Through the use of multiple climate scenarios from 12 regional climate model simulations, the ensemble mean, and three synthetic simulations generated by a weighting procedure, we investigated intermodel seasonal climate change signals between current and future periods, for both median and extreme precipitation/temperature values. A significant dependence of seasonal climate change signals on the model biases over southern Québec in Canada was detected for temperatures, but not for precipitation. This suggests that the regional temperature change signal is affected by local processes. Seasonally, model bias affects future mean and extreme values in winter and summer. In addition, potentially large increases in future extremes of temperature and precipitation values were projected. For three synthetic scenarios, systematically less bias and a narrow range of mean change for all variables were projected compared to those of climate model simulations. In addition, synthetic scenarios were found to better capture the spatial variability of extreme cold temperatures than the ensemble mean scenario. These results indicate that the synthetic scenarios have greater potential to reduce the uncertainty of future climate projections and capture the spatial variability of extreme climate events.
Keywords: Gachon_Philippe

Meteorological control on snow depth evolution and snowpack energy exchanges in an agro-forested environment by a measurement-based approach: A case study in Sainte-Marthe, Eastern Canada - Dharmadasa, Vasana; Kinnard, Christophe; Baraër, Michel (Agricultural and Forest Meteorology, 2024)
Keywords: Baraer_Michel; Kinnard_Christophe

Long-term variations of river ice breakup timing across Canada and its response to climate change - Chen, Yuzhuang; She, Yuntong (Cold Regions Science and Technology, 2020)
Abstract River ice breakup has extensive implications on cold-region hydrological, ecological and river morphological systems. However, spatial and temporal breakup patterns under the changing climate are not well explored on large scale. This study discusses the spatial-temporal variations of breakup timing over terrestrial ecozones and five selected river basins of Canada based on long-term (1950–2016) data record. The link between the discovered patterns and climatic drivers (including air temperature, snowfall and rainfall), as well as elevation and anthropogenic activities are analyzed. An overall earlier breakup trend is observed across Canada and the spring air temperature is found to be the main driver behind it. However, the most pronounced warming trends across Canada is observed in winter. Spring warming trend is not as strong as winter warming and even becomes weak as period changes from 1950–2016 to 1970–2016, resulting in more stations showing later and significant later breakup during 1970–2016. Breakup pattern also displays evident spatial differences. Significant earlier breakup trends are mainly seen in western Canada (e.g. the Nelson River basin) and Arctic where spring warming trends are evident. Later and mixed breakup trends are generally identified in regions with weak warming or even cooling trends, such as Atlantic Canada and the St. Lawrence River basin. Spring snowfall generally delays breakup. Spring rainfall usually advances breakup dates while winter-rainfall can also delay breakup through refreezing. The increased snowfall in the north and increased rainfall in the south may be the reason why breakup timing is more sensitive to climatic warming in lower latitude regions than in higher latitude regions. Additionally, breakup timing in main streams and large rivers appears to be less sensitive to the warming trend than the headwaters and small tributaries. Elevation and flow regulation are also found to be contributing factors to the changes in breakup timing.
MAG ID: 3025903967

Assimilation of SMAP brightness temperatures in environment and climate change Canada's new land surface parameterization scheme - Carrera, Marco L.; Belair, Stephane; Bilodeau, Bernard; Abrahamowicz, Maria; Alavi, Nasim; Russell, Albert; Wang, Xihong (2017 IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2017)

La réduction des risques de désastres : défis et possibilités pour le Québec et le Canada. Université du Québec à Montréal, Chaire de recherche UQAM sur les risques hydrométéorologiques liés aux changements climatiques - Boyer-Villemaire, U.; Gachon, P.; Boucher, E.; Germain, D.; Raphoz, M.; Doré, M. C.; Martin, J. P. (2017)
En marge de la Cinquième Plateforme régionale pour la Réduction des risques de catastrophes des Amériques (PRA), le gouvernement du Canada a approché l’Institut des sciences de l’environnement(ISE) de l’Université du Québec à Montréal(UQAM) afin d’organiser un forum public. Les échanges de ce dernier devaient servir à alimenter les discussions de la PRA. Au total, 21 experts ont discuté avec une centaine de participants lors de panels organisés à l’UQAM sous les thèmes de la santé, de la sécurité civile et de l’aménagement du territoire. Plusieurs thèmes transversaux ont aussi émergé tout au long du forum. Il importe de pérenniser le rôle de la recherche et d’améliorer les capacités de formation technique et universitaire afin de former des spécialistes en mesure d’appréhender la complexité de la gestion du risque dans un contexte de changements environnementaux et climatiques. Ceci est également essentiel pour l’identification des facteurs de risque (multisources ou multidimensionnels), pour tirer des leçons apprises des événements majeurs passés et récents, et pour développer ou mettre à jour la connaissance sur les tendances en cours et à venir des aléas météorologiques, ainsi que des facteurs de vulnérabilité et d’exposition. Tous les panels ont discuté de l’importance de favoriser le décloisonnement intra/interorganisationnel pour promouvoir la transsectorialité et les retours d’expériences systématiques. Pour ce faire, il faut s’inspirer des modèles internationaux, notamment du système d’alertes hydrométéorologiques présenté par Météo-France. Celui-ci inclut une vigilance météorologique qui cible des populations et des autorités publiques, et les informe des comportements et des règles à suivre lors d’alertes plus problématiques (vigilance aux stades orange et rouge). Finalement, l’amélioration de la communication et le libre accès à l’information sont des éléments essentiels pour protéger les individus et développer une société plus résiliente.
Keywords: Gachon_Philippe

Spaceborne L-Band Radiometry in Environment and Climate Change Canada (ECCC)’S Numerical Analysis and Prediction Systems - Belair, Stephane; Carrera, Marco L.; Abrahamowicz, Maria; Alavi, Nasim; Badawy, Bakr; Shahabadi, Maziar Bani; Bilodeau, Bernard; Charpentier, Dorothee; Deacu, Daniel; Durnford, Dorothy; Gaborit, Etienne; Gasset, Nicolas (IGARSS 2019 - 2019 IEEE International Geoscience and Remote Sensing Symposium, 2019)

Climate Variability and Change in Canada: Past, Present and Future - Barrow, Elaine; Maxwell, Barrie; Gachon, Philippe (Meteorological Service of Canada, Environment Canada, 2004)
Semantic Scholar extracted view of "CLIMATE VARIABILITY AND CHANGE IN CANADA" by E. Barrow et al.
Keywords: Gachon_Philippe; Ouvrage_Collectif_Numéro1

Climate change more than doubled the likelihood of extreme fire weather conditions in Eastern Canada - Barnes, C; Boulanger, Y; Keeping, T; Gachon, P; Gillett, N; Haas, O; Wang, X; Roberge, F; Kew, S; Heinrich, D; Singh, R; Vahlberg, M; et al. (2023)
Keywords: Gachon_Philippe

Landscape and climate conditions influence the hydrological sensitivity to climate change in eastern Canada - Aygün, Okan; Kinnard, Christophe; Campeau, Stéphane; Pomeroy, John W. (Journal of Hydrology, 2022)
Keywords: Kinnard_Christophe

Climate Change Impacts on Catchment Hydrology in Eastern Canada - Aygün, O.; Kinnard, C.; Campeau, S. (2019)
Snowmelt dominated regions are receiving increasing attention due to their noticeably rapid response to ongoing climate change, which raises concerns about the altered hydrological risks under climate change scenarios. This study aims to assess the climate change impacts on hydrology over two contrasted catchments in southern Québec: Acadie River and Montmorency River catchments. These river catchments represent two predominant landscapes of the St. Lawrence River watershed; an intensive farming landscape in the south shore lowlands and the forested landscape on the Canadian Shield on the north shore, respectively. In this study, a physically based hydrological model has been developed using the Cold Regions Hydrological Model (CRHM) for both of the catchments. The hydrological model outputs showed that we were able to simulate snow surveys and discharge measurements with a reasonable accuracy for both catchments. The acceptable performance of the model along with the strong physical basis of structure suggested that this model could be used for climate change sensitivity simulations. Based on the climate scenarios reviewed, a temperature increase up to 8°C and an increase in total precipitation up to 20% were analysed for both of the catchments. Both catchments were found to be sensitive to climate change, however the degree of sensitivity was found to be catchment specific. Snow processes in the Acadie River catchment were simulated to be more sensitive to warming than in the Montmorency River catchment. In case of 2°C warming, reduction in peak SWE was not be able to be compensated even by increased precipitation scenario. Given that, the Acadie River has already a mixed flow regime, even if 2°C warming is combined with an increase in precipitation, pluvial regime kept becoming more dominant, resulting in higher peaks of rain events. On the other hand, even 3°C of warming did not modify the flow regime of the Montmorency River. While there is shift towards earlier peak spring flows in both catchments, the shift was found to be more pronounced in the Acadie River. An earlier occurrence of snowmelt floods and an overall increase in winter streamflow during winter have been simulated for both catchments, which calls for renewed assessments of existing water supply and flood risk management strategies.
Conference Name: AGU Fall Meeting Abstracts ADS Bibcode: 2019AGUFM.C33B1572A
Keywords: Kinnard_Christophe

Analysis of the impacts of climate change, physiographic factors and land use/cover on the spatiotemporal variability of seasonal daily mean flows in southern Quebec (Canada) - Assani, Ali A. (Applied Water Science, 2024)
Abstract The objective of this study is to compare the spatiotemporal variability of seasonal daily mean flows measured in 17 watersheds, grouped into three homogeneous hydroclimatic regions, during the period 1930–2023 in southern Quebec. With regard to spatial variability, unlike extreme daily flows, seasonal daily mean flows are very poorly correlated with physiographic factors and land use and land cover. In fall, they are not correlated with any physiographic or climatic factor. In winter, they are positively correlated with the rainfall and winter daily mean maximum temperatures. In spring, they are strongly correlated positively with the snowfall but negatively with the spring daily mean maximum temperatures. However, in summer, they are better correlated with forest area and, to a lesser extent, with the rainfall. As for their temporal variability, the application of six different statistical tests revealed a general increase in daily mean flows in winter due to early snowmelt and increased rainfall in fall. In summer, flows decreased significantly in the snowiest hydroclimatic region on the south shore due to the decrease in the snowfall. In spring, no significant change in flows was globally observed in the three hydroclimatic regions despite the decrease in the snowfall due to the increase in the rainfall. In fall, flows increased significantly south of 47°N on both shores due to the increase in the rainfall. This study demonstrates that, unlike extreme flows, the temporal variability of seasonal daily average flows is exclusively influenced by climatic variables in southern Quebec. Due to this influence, seasonal daily mean flows thus appear to be the best indicator for monitoring the impacts of changes in precipitation regimes and seasonal temperatures on river flows in southern Quebec.
Keywords: Infolettre; Infolettre_Mai_2024

The impact of climate change on rivers and river processes in Canada - Ashmore, P; Church, M (2001)
Rivers are sensitive to natural climate change as well as to human impacts such as flow modification and land-use change. Climate change could cause changes to precipitation amounts, the intensity of cyclonic storms, the proportion of precipitation falling as rain, glacier mass balance, and the extent of permafrost; all of which affect the hydrology and morphology of river systems. Changes to the frequency and magnitude of flood flows present the greatest threat. Historically, wetter periods are associated with significantly higher flood frequency and magnitude. These effects are reduced in drainage basins with large lakes or glacier storage. Alluvial rivers with fine-grained sediments are most sensitive, but all rivers will respond, except those flowing through resistant bedrock. The consequences of changes in flow include changes in channel dimensions, gradient, channel pattern, sedimentation, bank erosion rates, and channel migration rates. The most sensitive and vulnerable regions are in southern Canada, particularly those regions at risk of substantial increases in rainfall intensity and duration. In northern rivers, thawing of permafrost and changes to river-ice conditions are important concerns. The type and magnitude of effects will be different between regions, as well as between small and large river basins. Time scales of change will range from years to centuries. These changes will affect the use that we make of rivers and their floodplains, and may require mitigative measures. Radical change is also possible. Climatic impacts will be ubiquitous and will be in addition to existing and future direct human impact on streamflow and rivers.
Report Number: 555
Keywords: Ouvrage_Collectif_Numéro1

Future realities of climate change impacts: an integrated assessment study of Canada - Akhtar, Mohammad Khaled; Simonovic, Slobodan P.; Wibe, Jacob; MacGee, James (International Journal of Global Warming, 2019)
This paper presents an integrated assessment model for use with climate policy decision making in Canada. The feedback based integrated assessment model ANEMI_CDN represents Canada within the global society-biosphere-climate-economy-energy system. The model uses a system dynamics simulation approach to investigate the impacts of climate change in Canada and policy options for adapting to changing global conditions. The disaggregation techniques allow ANEMI_CDN to show results with various temporal resolutions. Two Canadian policy scenarios are presented as illustrative examples to map policy impacts on key model variables, including population, water-stress, food production, energy consumption, and emissions under changing climate over this century. The main finding is a significant impact of a carbon tax on energy consumption. Two policy scenario simulations provide additional insights to policy makers regarding the choice of adaptation/mitigation options along with their implementation time.
MAG ID: 2900571356

Setting Targets for Wetland Restoration to Mitigate Climate Change Effects on Watershed Hydrology - Goyette, Jean-Olivier; Savary, Stéphane; Blanchette, Marianne; Rousseau, Alain N.; Pellerin, Stéphanie; Poulin, Monique (Environmental Management, 2023)
Keywords: Infolettre; Infolettre_Fevrier_2023; Rousseau_Alain

Can isolated and riparian wetlands mitigate the impact of climate change on watershed hydrology? A case study approach - Fossey, Maxime; Rousseau, Alain N. (Journal of Environmental Management, 2016)
The effects of wetlands on stream flows are well established, namely mitigating flow regimes through water storage and slow water release. However, their effectiveness in reducing flood peaks and sustaining low flows is mainly driven by climate conditions and wetland type with respect to their connectivity to the hydrographic network (i.e. isolated or riparian wetlands). While some studies have demonstrated these hydrological functions/services, few of them have focused on the benefits to the hydrological regimes and their evolution under climate change (CC) and, thus, some gaps persist. The objective of this study was to further advance our knowledge with that respect. The PHYSITEL/HYDROTEL modelling platform was used to assess current and future states of watershed hydrology of the Becancour and Yamaska watersheds, Quebec, Canada. Simulation results showed that CC will induce similar changes on mean seasonal flows, namely larger and earlier spring flows leading to decreases in summer and fall flows. These expected changes will have different effects on 20-year and 100-year peak flows with respect to the considered watershed. Nevertheless, conservation of current wetland states should: (i) for the Becancour watershed, mitigate the potential increase in 2-year, 20-year and 100-year peak flows; and (ii) for the Yamaska watershed, accentuate the potential decrease in the aforementioned indicators. However, any loss of existing wetlands would be detrimental for 7-day 2-year and 10-year as well as 30-day 5-year low flows.
MAG ID: 2530043799
Keywords: Rousseau_Alain

Spatially Disaggregated Assessment of Environmental Inequalities Among Vulnerable Groups due to Urban Rainstorm Flooding - Bosisio, Andrea Cecilia; Jiménez, Antonio Moreno (Applied Spatial Analysis and Policy, 2022)
MAG ID: 4281957753

An Integrated Extreme Rainfall Modeling Tool (SDExtreme) for Climate Change Impacts and Adaptation - Yeo, Myeong-Ho; Nguyen, Van-Thanh-Van; Kim, Yong Sang; Kpodonu, Theodore A. (Water Resources Management, 2022)
Abstract The estimation of the Intensity–Duration–Frequency (IDF) relation is often necessary for the planning and design of various hydraulic structures and design storms. It has been an increasingly greater challenge due to climate change conditions. This paper therefore proposes an integrated extreme rainfall modeling software package (SDExtreme) for constructing the IDF relations at a local site in the context of climate change. The proposed tool is based on a temporal downscaling method to describe the relationships between daily and sub-daily extreme precipitation using the scale-invariance General Extreme Value (GEV) distribution. In addition, SDExtreme provides a modified bootstrap technique to determine confidence intervals (CIs) of the estimated IDF curves for current and the future climate conditions. The feasibility and accuracy of SDExtreme were assessed using rainfall data available from the selected rain gauge stations in Quebec and Ontario provinces (Canada) and climate simulations under three different climate change scenarios provided by the Canadian Earth System Model (CanESM2) and the Canadian Regional Climate Model (CanRCM4).
Keywords: Infolettre; Infolettre_Juillet_2022; Site_internet_RIISQ

Environmental justice and flood prevention: The moral cost of floodwater redistribution - Liao, Kuei-Hsien; Chan, Jeffrey; Huang, Yin-Ling (Landscape and Urban Planning, 2019)
MAG ID: 2942343860

Editorial: Building flood resilience under climate change - Wang, Xander; Nguyen, Van-Thanh-Van; Zhou, Xiong; Najafi, Mohammad Reza (Frontiers in Environmental Science, 2024)
Keywords: Infolettre; Infolettre_Fevrier_2024

L'approche écosystémique de la santé des populations : le cas de l’exposition au mercure des communautés riveraines de l’Amazonie et du nord du Québec - Weissenberger, Sebastian; Silva, Delaine Sampaio Da; Schetagne, Roger (Développement durable et territoires, 2013)

Operating urban resilience strategies to face climate change and associated risks: some advances from theory to application in Canada and France - Heinzlef, Charlotte; Robert, Benoît; Hémond, Yannick; Serre, Damien (Cities, 2020)
Keywords: Hémond_Yannick; Ouvrage_Collectif_Numéro1

Transformative learning for a sustainable and healthy future through ecosystem approaches to health: insights from 15 years of co-designed ecohealth teaching and learning experiences - Webb, Jena; Raez-Villanueva, Sergio; Carrière, Paul D; Beauchamp, Audrey-Anne; Bell, Isaac; Day, Angela; Elton, Sarah; Feagan, Mathieu; Giacinti, Jolene; Kabemba Lukusa, Jean Paul; Kingsbury, Celia; Torres-Slimming, Paola A; et al. (The Lancet Planetary Health, 2023)

Social inequalities in climate change-attributed impacts of Hurricane Harvey. - Smiley, Kevin T.; Noy, Ilan; Wehner, Michael F.; Frame, Dave; Sampson, Christopher C.; Wing, Oliver E J (Nature Communications, 2022)
Climate change is already increasing the severity of extreme weather events such as with rainfall during hurricanes. But little research to date investigates if, and to what extent, there are social inequalities in climate change-attributed extreme weather event impacts. Here, we use climate change attribution science paired with hydrological flood models to estimate climate change-attributed flood depths and damages during Hurricane Harvey in Harris County, Texas. Using detailed land-parcel and census tract socio-economic data, we then describe the socio-spatial characteristics associated with these climate change-induced impacts. We show that 30 to 50% of the flooded properties would not have flooded without climate change. Climate change-attributed impacts were particularly felt in Latina/x/o neighborhoods, and especially so in Latina/x/o neighborhoods that were low-income and among those located outside of FEMA's 100-year floodplain. Our focus is thus on climate justice challenges that not only concern future climate change-induced risks, but are already affecting vulnerable populations disproportionately now.
MAG ID: 4293090391

Le Rapport 2023 du Lancet Countdown sur la santé et les changements climatiques: l’impératif d’une démarche axée sur la santé dans un monde confronté à des dommages irréversibles - Romanello, Marina; di Napoli, Claudia; Green, Carole; Kennard, Harry; Lampard, Pete; Scamman, Daniel; Walawender, Maria; Ameli, Nadia; Ayeb-Karlsson, Sonja; Beggs, Paul J; Belesova, Kristine; Ford, Lea Berrang; et al. (2023)

Scenarios of Human Responses to Unprecedented Social‐Environmental Extreme Events - Rusca, Maria; Messori, Gabriele; Di Baldassarre, Giuliano (Earth's Future, 2021)
Abstract In a rapidly changing world, what is today an unprecedented extreme may soon become the norm. As a result, extreme‐related disasters are expected to become more frequent and intense. This will have widespread socio‐economic consequences and affect the ability of different societal groups to recover from and adapt to rapidly changing environmental conditions. Therefore, there is the need to decipher the relation between genesis of unprecedented events, accumulation and distribution of risk, and recovery trajectories across different societal groups. Here, we develop an analytical approach to unravel the complexity of future extremes and multiscalar societal responses—from households to national governments and from immediate impacts to longer term recovery. This requires creating new forms of knowledge that integrate analyses of the past—that is, structural causes and political processes of risk accumulation and differentiated recovery trajectories—with plausible scenarios of future environmental extremes grounded in the event‐specific literature. We specifically seek to combine the physical characteristics of the extremes with examinations of how culture, politics, power, and policy visions shape societal responses to unprecedented events, and interpret the events as social‐environmental extremes. This new approach, at the nexus between social and natural sciences, has the concrete advantage of providing an impact‐focused vision of future social‐environmental risks, beyond what is achievable within conventional disciplinary boundaries. In this paper, we focus on extreme flooding events and the societal responses they elicit. However, our approach is flexible and applicable to a wide range of extreme events. We see it as the first building block of a new field of research, allowing for novel and integrated theoretical explanations and forecasting of social‐environmental extremes. , Key Points We conceptualize unprecedented extremes as social‐environmental processes shaped by institutional, political, and economic change As social‐environmental extremes become more frequent, there is an urgency to unravel their genesis and the possible societal responses This approach is the first building block of a new field of research in social‐environmental extreme event forecasts , Plain Language Summary The world is seeing increases in a range of extreme events, and this increase may continue or even accelerate in the future, due to anthropogenic climate change. Furthermore, it is often those who are already vulnerable that experience the biggest impacts from these extremes. Yet, there is little understanding of the possible societal responses to unprecedented events. This underscores the urgency of creating innovative approaches to develop plausible scenarios of societal responses and, in turn, mitigate hazards and reduce vulnerability and exposure to extreme events. In this commentary, we develop a truly interdisciplinary conceptual approach to better understand how different societal groups might interact with and respond to future unprecedented extreme events. We combine social science theories describing how different societal groups are affected by, and recover from, extreme events with projections from the literature identifying plausible areas at risk of unprecedented occurrences and local analyses of past extreme events. We see this as the first building block of a new field of research in forecasting social‐environmental extremes that could support governments, civil protection agencies, and civil society organizations to ensure a fairer, improved response to future events.

Snow particles physiochemistry: feedback on air quality, climate change, and human health - Rangel-Alvarado, Rodrigo; Li, Houjie; Ariya, Parisa A. (Environmental Science: Atmospheres, 2022)
During the last several decades, numerous researchers have provided evidence that physical and biogeochemical processes at air-snow/ice-water interfaces are very complex, and, in many cases, interlinked. , During the last several decades, numerous researchers have provided evidence that physical and biogeochemical processes at air-snow/ice-water interfaces are very complex, and, in many cases, interlinked. This review focuses on the current state of knowledge regarding snow-borne particles. It integrates snow science from different angles: from the formation of snow and precipitation to transformations through natural and anthropogenic processes and impacts and snow management in urban areas sites. We discuss the physical, chemical, and biological characteristics of particles in snow, such as their composition, abundance, size distribution, ice nucleation properties, genomic features, and microphysical processes, in urban settings, remote areas of the Arctic, and remote industrial regions (oil sands). We explore physicochemical processes of snow particles: from microbial to emerging contaminants, like nano/microplastics, light-absorbing carbonaceous organics, halogenated and nanometals particles. We review the possible contributions of snow particles to atmospheric radiation and climate, biogeochemistry, human health, and urban snow management. We propose further research directions to improve understanding of air-snow feedback, and sustainable snow management in urban areas, in the age of emerging contaminants in a changing climate.

Mortgage Finance and Climate Change: Securitization Dynamics in the Aftermath of Natural Disasters - Ouazad, Amine; Kahn, Matthew (National Bureau of Economic Research, 2019)
Keywords: Ouvrage_Collectif_Numéro1

Les impacts des changements climatiques sur la santé au Québec : l’exemple de l’Estrie - Petit, Geneviève; Lachance, Éric; Généreux, Mélissa; Barbeau-Meunier, Charles-Antoine; Pinsonneault, Linda; Dao, Huy Hao; Milot, Marie-Christine; Baron, Geneviève; Carignan, Alex (Le Climatoscope, 2019)
L’Organisation mondiale de la Santé (OMS) soutient que les changements climatiques représentent la plus grande menace pour la santé dans le monde au 21e siècle. Ceux-ci influencent négativement plusieurs déterminants sociaux et environnementaux de la santé comme l’accessibilité à la nourriture et la qualité de cette dernière, l’eau et l’air. Blessures, impacts psychosociaux, aggravation de maladies respiratoires, malnutrition, maladies infectieuses, décès : les conséquences sanitaires sont susceptibles d’affecter les populations sur tous les continents. Le Canada se réchauffe deux fois plus rapidement que la moyenne mondiale en raison de sa proximité au pôle Arctique, où le réchauffement est accéléré comparativement à l’équateur (Bush et Lemmen, 2019). Ainsi, le Québec n’est certainement pas à l’abri des changements climatiques. Dans le Sud de la province, les températures moyennes observées ont augmenté de plus d’un degré depuis 1970 et des répercussions se font déjà sentir dans notre environnement. Ce réchauffement, accompagné d’une plus grande variabilité du climat (augmentation du risque d’orages, de tempêtes et d’extrêmes hydrométéorologiques en général), représente un défi grandissant pour les professionnel.le.s de la santé. Dans la région de l’Estrie, les professionnel.le.s de santé publique ont effectué une analyse qui leur ont permis d’identifier quatre principaux problèmes environnementaux associés aux changements climatiques, soit : les vagues de chaleur; les inondations; les tiques à pattes noires; le pollen de l’herbe à poux. Ces problèmes ont des impacts importants sur la santé, c’est-à-dire potentiellement graves ou qui touchent un grand nombre de personnes. Le stress et les pertes (humaines et matérielles) engendrées par ces différents problèmes environnementaux peuvent aussi représenter une source majeure de problèmes psychologiques significatifs pouvant persister dans le temps. De plus, ces impacts sont variables selon les différents contextes sociaux des individus et des communautés, générant des inégalités sociales de santé.
Keywords: Généreux_Mélissa

Chapitre 27 Santé mentale, changement climatique et pratique infirmière - Lessard, L.; Turmel, J.; Lafond, A. (Soins infirmiers en psychiatrie et santé mentale, 2023)

Eco-anxiety in children: A scoping review of the mental health impacts of the awareness of climate change - Léger-Goodes, Terra; Malboeuf-Hurtubise, Catherine; Mastine, Trinity; Généreux, Mélissa; Paradis, Pier-Olivier; Camden, Chantal (Frontiers in Psychology, 2022)
Background Youth are increasingly aware of the negative effects of climate change on the planet and human health, but this knowledge can often come with significant affective responses, such as psychological distress, anger, or despair. Experiencing major “negative” emotions, like worry, guilt, and hopelessness in anticipation of climate change has been identified with the term eco-anxiety. Emerging literature focuses on adults' experience; however, little is known about the ways in which children and youth experience eco-anxiety. Objectives The aim of this review was to: (1) identify the available evidence on the topic of eco-anxiety in children, (2) clarify the mental health consequences brought by the awareness of climate change in this population, and (3) identify knowledge gaps in the literature and considerations for future research. Methods Given that the research on the topic of eco-anxiety in children is limited, that there are very few randomized controlled trials, and that the goal is not to analyze individual studies in-depth, a scoping review was used. Keywords pertaining to the themes of eco-anxiety, climate change and children (aged < 18 years) were used as search terms in five databases. Journal articles using qualitative and quantitative methods, as well as gray literature were examined by two independent reviewers. A descriptive-analytical method was used to chart the data that emerged from the literature. Eighteen articles were considered in the final analysis. Results Evidence confirms that children experience affective responses and eco-anxiety in reaction to then awareness of climate change. Mental health outcomes include depression, anxiety, and extreme emotions like sadness, anger, and fear. Youth from vulnerable communities, like indigenous communities, or those who have strong ties to the land are often identified as being emotionally impacted by climate change. The literature analyzed also describes how children and youth are coping with eco-anxiety, including maladaptive (e.g., denial) and adaptive responses (such as constructive hope, used as a positive coping mechanism). Preliminary considerations for parents, teachers and educators, mental health care providers, school systems, adults and people of power include adding age-appropriate climate education to the school curriculum, considering youth's emotions, and promoting healthy coping through empowerment. Important gaps exist in the definition of eco-anxiety in youth, as various characterizations of this emerging concept are found across articles.
Keywords: Généreux_Mélissa

Measuring the total economic value of restoring ecosystem services in an impaired river basin: results from a contingent valuation survey - Loomis, John; Kent, Paula; Strange, Liz; Fausch, Kurt; Covich, Alan (Ecological Economics, 2000)
Keywords: Ouvrage_Collectif_Numéro1

Interregional imbalance in the Yellow River Basin: Insights from flood-sediment transport, socioeconomic, and environmental subsystems - Hu, Hao; Tian, Guiliang; Adamowski, Jan F.; Albano, Raffaele; Liu, Yixue; Jing, Xiaodong; Zhao, Qiuya (Journal of Environmental Management, 2024)
Keywords: Infolettre; Infolettre_Decembre_2024

Climate change, poverty and child health inequality: evidence from Vietnam’s provincial analysis - Huynh, Cong Minh; Tran, Bao Khuyen (Economic Change and Restructuring, 2024)

Mesurer et prédire l'adaptation aux changements climatiques dans les municipalités québécoises : Développement et validation d'indices et mesure des déterminants psychosociaux de l'action - Jacob, Johann (2022)
Publisher: Unpublished

Pistes d'interventions psychosociales pour préserver les jeunes des impacts des catastrophes naturelles ou technologiques - Lansard, Anne-Lise; Maltais, Danielle; Généreux, Mélissa (2020)
Cette recension a pour objectifs de documenter les approches et les principes d'intervention recommandés dans les écrits pour intervenir auprès des jeunes en contexte de catastrophe, de décrire des techniques, des stratégies, des programmes et des types d'intervention ayant déjà été mis en place auprès d'enfants et d'adolescents en contexte de catastrophe et d'identifier les facteurs ayant contribué à l'efficacité des interventions.
Num Pages: 159
Keywords: Généreux_Mélissa; Ouvrage_Collectif_Numéro1; Site_internet_RIISQ

Responding to a Changing Climate: An Investigation of the Psychosocial Consequences of Climate Change and Community-based Mental Health Responses in High River - Hayes, K. (2019)
This dissertation explores the psychosocial consequences of climate change and psychosocial adaptation opportunities in High River, Alberta. Influenced by the theoretical approach of Political Ecology, I investigate community impacts and community-based mental health responses in High River following the 2013 Southern Alberta floods. Research methods include: a desktop climate change and health vulnerability and adaptation assessment that includes over 116 data sources; telephone interviews with key informant health and social services leaders (n = 14); four focus group sessions with front-line health and social services workers (n = 14); and, semi-structured interviews (n = 18) with a sample of community-members exposed to the 2013 flood and who self-identify in any one or more ways: female, youth, elderly, non-white, someone living in a low socio-economic status, someone with pre-existing health concerns. A total of 46 participants were recruited in this research. Results of the empirical investigation in High River are showcased in three manuscripts. The first manuscript, informed by critical Political Ecology, is an investigation of sociopolitical conditions that influence health inequities and adaptation opportunities (or lack thereof) in a changing climate in High River. The second is an empirical exploration of the long-term psychosocial consequences of the 2013 flood, relating these

From Science to Policy and Practice: A Critical Assessment of Knowledge Management before, during, and after Environmental Public Health Disasters - Généreux, Mélissa; Lafontaine, Marc; Eykelbosh, Angela (International Journal of Environmental Research and Public Health, 2019)
Canada regularly faces environmental public health (EPH) disasters. Given the importance of evidence-based, risk-informed decision-making, we aimed to critically assess the integration of EPH expertise and research into each phase of disaster management. In-depth interviews were conducted with 23 leaders in disaster management from Canada, the United States, the United Kingdom, and Australia, and were complemented by other qualitative methods. Three topics were examined: governance, knowledge creation/translation, and related barriers/needs. Data were analyzed through a four-step content analysis. Six critical success factors emerged from the analysis: blending the best of traditional and modern approaches; fostering community engagement; cultivating relationships; investing in preparedness and recovery; putting knowledge into practice; and ensuring sufficient human and financial resources. Several promising knowledge-to-action strategies were also identified, including mentorship programs, communities of practice, advisory groups, systematized learning, and comprehensive repositories of tools and resources. There is no single roadmap to incorporate EPH expertise and research into disaster management. Our findings suggest that preparation for and management of EPH disaster risks requires effective long-term collaboration between science, policy, and EPH practitioners at all levels in order to facilitate coordinated and timely deployment of multi-sectoral/jurisdictional resources when and where they are most needed.
Keywords: Généreux_Mélissa

Health impacts of climate change in the UK: A qualitative synthesis detailing the conjuncture of social structure, extreme weather, and mental health - Dodd, Steven; Kragh-Furbo, Mette; Davies, Jessica; Butterfield, Scott; Morris, Abigail; Brown, Heather (SSM - Qualitative Research in Health, 2024)

Economic losses from US hurricanes consistent with an influence from climate change - Estrada, Francisco; Botzen, W. J. Wouter; Tol, Richard S.J. (Nature Geoscience, 2015)
The observed increases in hurricane losses are often thought to result solely from societal change. A regression-based analysis of US economic losses reveals an upward trend between 1900 and 2005 that is not explained by increasing vulnerability.
MAG ID: 2240711578

Discussing linkages between climate change, human mobility and health in the Caribbean: The case of Dominica. A qualitative study - Cloos, Patrick; Belloiseau, Maeva; Mc Pherson, Nickez; Harris-Glenville, Fiona; Joseph, Debra D.; Zinszer, Kate (The Journal of Climate Change and Health, 2023)
Keywords: Cloos_Patrick

Research on climate change, health inequities, and migration in the Caribbean - Cloos, Patrick; Ridde, Valéry (The Lancet Planetary Health, 2018)
Keywords: Cloos_Patrick

Climate Change and Occupational Health and Safety in a Temperate Climate: Potential Impacts and Research Priorities in Quebec, Canada - Adam-Poupart, Ariane; Labrèche, France; Smargiassi, Audrey; Duguay, Patrice; Busque, Marc-Antoine; Gagné, Charles; Rintam, Hannu; Kjellstrom, Tord; Zayed, Joseph (Industrial Health, 2013)

Un cadre de gouvernance collaboratif dédié à l’appréciation des risques des systèmes essentiels dans un contexte de changements climatiques - Robert, Benoît; Hémond, Yannick; Baril, Geneviève; Therrien, Marie-Christine (Canadian Journal of Emergency Management, 2022)
The fall 2021 climate events in British Columbia raise questions about the resiliency of communities, but also of critical systems, with respect to the allocation of roads, telecommunications, drinking water, electricity, etc. The interdependence of these systems can quickly generate serious consequences for populations and socio-economic activities that local and regional authorities must manage. The diversity and number of stakeholders require these authorities to coordinate well. How then can the risks to which they are exposed be better assessed? How can we ensure coherence in the measures put in place in terms of planning, preparation and response? The concepts and results presented in this article are the result of an action-research project carried out with the participation of numerous partners, particularly, but not exclusively, from municipal milieus in two regions of Quebec (Argenteuil and Brome-Missisquoi MRCs). This active collaboration with these regional partners has made it possible to propose an approach for implementing a collaborative governance framework combined with a risk assessment process. The tools and mechanisms associated with this approach will allow regional authorities to better understand the impact of climate change on the territory and to ensure consistency in the risk management actions of the various stakeholders. , Les événements climatiques de l’automne 2021 en Colombie-Britannique soulèvent des questions sur la résilience des communautés, mais aussi des systèmes essentiels, en regard de l’affectation des réseaux routiers, de télécommunication, d’eau potable, d’électricité, etc. L’interdépendance de ces systèmes génère rapidement des conséquences graves pour la population et les activités socioéconomiques que les autorités locales et régionales doivent gérer. La diversité des intervenants ainsi que leur nombre exigent de ces autorités de bien se coordonner. Comment alors peut-on mieux apprécier les risques auxquels ils sont exposés ? Comment s’assurer d’une cohérence dans les mesures mises en place autant dans la planification, la préparation que l’intervention ? Les concepts et résultats présentés dans cet article sont issus d’un projet de recherche-action réalisé avec la participation de nombreux partenaires, particulièrement, mais non exclusivement du milieu municipal dans deux régions du Québec (MRC d’Argenteuil et de Brome-Missisquoi). Cette collaboration active avec ces partenaires régionaux permet de proposer une démarche pour mettre en place un cadre de gouvernance collaboratif combiné à un processus d’appréciation des risques. Les outils et mécanismes associés à cette démarche permettront, alors, aux autorités régionales de mieux comprendre l’impact des changements climatiques sur le territoire et d’assurer une cohérence dans les actions de gestion des risques des différentes parties prenantes.
Keywords: Hémond_Yannick

Gouvernance régionale et stratégies d’adaptation aux inondations en contexte de changements climatiques : une étude de cas, la MRC de Vaudreuil-Soulanges - Thivierge, Caroline (2021)
L’objectif de cette recherche est d’identifier les stratégies d’adaptation qui sont requises et du ressort d’une municipalité régionale de comté face aux inondations. Le réchauffement global des températures soulève plusieurs inquiétudes quant à la modification du cycle hydrologique. Les inondations figurent en tête de liste des enjeux de sécurité civile des municipalités riveraines. Au Québec, on prévoit une augmentation des précipitations printanières, automnales et hivernales, ainsi que des débits hivernaux plus élevés et un devancement des crues printanières. Des projections qui peuvent influencer l’approche de gestion des barrages, bien que le contrôle des niveaux d’eau ne soit pas une panacée vis-à-vis des inondations. Il suppose une gestion intégrée de l’eau parfois complexe. Aussi, les administrations locales ne siègent pas toujours aux comités responsables de la régularisation des cours d’eau. Celles-ci se retrouvent sur la ligne de front sans pour autant avoir le pouvoir et les ressources financières pour y faire face. Les crues exceptionnelles de 2017 et 2019 ont conduit la Municipalité régionale de comté de Vaudreuil-Soulanges à mettre à jour ses plans d’urgence et à mettre en place une cellule de crise. Elle applique une stratégie d’adaptation correspondant aux 4 axes du Plan de protection du territoire face aux inondations du ministère des Affaires municipales et de l’Habitation. Ces outils enrichissent leur capacité d’adaptation par l’acquisition de nouvelles connaissances et d’une nouvelle cartographie des zones inondables. Les vulnérabilités qui résultent de contraintes liées à l’aménagement du territoire, ainsi que d’enjeux réglementaires posent un défi pour le développement du territoire et la relocalisation de résidences inondées. Il convient de sonder la population sur sa vision de la résilience afin d’assurer une meilleure acceptabilité sociale des décisions à venir. Une vulnérabilité importante réside dans les écarts de perception du risque entre les municipalités et entre les individus ; ce qui engendre des enjeux de sécurité, de communication et de gouvernance. Les instances locales peuvent miser sur leurs habiletés de mobilisation pour réunir la communauté autour du développement d’un plan d’adaptation aux changements climatiques et ainsi harmoniser les perceptions. Finalement, l’épuisement des ressources humaines des municipalités inondées à répétition est à considérer. Il appert qu’il est essentiel d’identifier et de mettre en place les outils et ressources pour les soutenir.
Keywords: Ouvrage_Collectif_Numéro1

The challenge of SMBs resilience in urban governance. The case of SMBs and climate change - Robert, Benoît; Hémond, Y. (2017)
Keywords: Hémond_Yannick

Stratégie pour les sciences 2024 à 2029 d’Environnement et Changement climatique Canada - Gouvernement du Canada (2024)
Cette stratégie oriente les activités scientifiques d'Environnement et Changement climatique Canada afin de favoriser un avenir plus vert et plus durable. Elle met l'accent sur nos gens, nos valeurs et nos priorités tournées vers l'avenir en tant que ministère fédéral à vocation scientifique.
Last Modified: 2024-02-16

Zones inondables – Réalisations par le gouvernement du Québec - Ministère de l’Environnement et de la Lutte contre les changements climatiques (MELCC) (Gouvernement du Québec, 2021)
Keywords: Ouvrage_Collectif_Numéro1

Inclusion démocratique : retour sur un cas de gouvernance décentrée de l’adaptation aux changements climatiques - Létourneau, Alain (Le Climatoscope, 2020)
Parler d’inclusion démocratique, c’est chercher à impliquer les citoyen.ne.s dans les processus de prise de décision des organes politiques. Évidemment la première question qui vient, c’est celle de savoir comment le faire. Cette tâche complexe se joue sur de multiples échelles : au niveau national, au niveau des provinces ou des états, des régions, des villes; […]
Keywords: Site_internet_RIISQ

Gouvernance collaborative d'appréciation des risques des systèmes essentiels en contexte de changements climatiques : cas de deux MRC au Québec - Lépine, Caroline; Baril, Geneviève; Hémond, Yannick; Therrien, M.-C.; Robert, Benoît (2019)
Keywords: Hémond_Yannick

L’autogouvernement et la gouvernance: Réflexion à partir d’un projet d’adaptation aux changements climatiques sur le territoire de la MRC de Memphrémagog - Létourneau, Alain (Sens public, 2019)
Keywords: Ouvrage_Collectif_Numéro1; Site_internet_RIISQ

Réchauffement planétaire de 1,5 °C, Rapport spécial du GIEC sur les conséquences d’un réchauffement planétaire de 1,5 °C par rapport aux niveaux préindustriels et les trajectoires associées d’émissions mondiales de gaz à effet de serre, dans le contexte du renforcement de la parade mondiale au changement climatique, du développement durable et de la lutte contre la pauvreté - Groupe d’experts intergouvernemental sur l’évolution du climat (GIEC) (Organisation météorologique mondiale, 2018)
ISBN 978-92-9169-253-8
Keywords: Ouvrage_Collectif_Numéro1

Everyday governance and urban environments: Towards a more interdisciplinary urban political ecology - Cornea, Natasha Lee; Véron, René; Zimmer, Anna (Geography Compass, 2017)
Abstract Urban political ecology (UPE) has mainly evolved within the discipline of geography to examine the power relations that produce uneven urban spaces (infrastructures and natures) and unequal access to resources in cities. Its increasingly poststructuralist orientation demands the questioning of received categories and concepts, including those of (neoliberal) governance, government, and of the state. This paper attempts to open this black box by referring to the mostly anthropological literature on everyday governance and the everyday state. We argue that UPE could benefit from ethnographic governance studies to unveil multiple state and non‐state actors that influence the local environment, their diverse rationalities, normative registers, and interactions across scales. This would also to enrich and nuance geographical UPE accounts of neoliberal environmental governance and potentially render the framework more policy relevant.
Keywords: Ouvrage_Collectif_Numéro1

Managing the Risks of Extreme Events and Disasters to Advance Climate Change Adaptation, A Special Report of Working Groups I and II of the Intergovernmental Panel on Climate Change - Intergovernmental Panel on Climate Change (IPCC) (Cambridge University Press, 2012)
Keywords: Ouvrage_Collectif_Numéro1

Changements climatiques, changements du littoral et évolution de la vulnérabilité côtière au fil du temps : comparaison de territoires français, canadien et sénégalais - Weissenberger, Sebastian; Noblet, Mélinda; Plante, Steve; Chouinard, Omer; Guillemot, Julie; Aubé, Mélanie; Meur-Ferec, Catherine; Michel-Guillou, Élisabeth; Gaye, Ndickou; Kane, Alioune; Kane, Coura; Niang, Awa; et al. (2016)

On the relation between weather-related disaster impacts, vulnerability and climate change - Visser, Hans; Petersen, Arthur C.; Ligtvoet, Willem (Climatic Change, 2014)
Disasters such as floods, storms, heatwaves and droughts can have enormous implications for health, the environment and economic development. In this article, we address the question of how climate change might have influenced the impact of weather-related disasters. This relation is not straightforward, since disaster burden is not influenced by weather and climate events alone—other drivers are growth in population and wealth, and changes in vulnerability. We normalized disaster impacts, analyzed trends in the data and compared them with trends in extreme weather and climate events and vulnerability, following a 3 by 4 by 3 set-up, with three disaster burden categories, four regions and three extreme weather event categories. The trends in normalized disaster impacts show large differences between regions and weather event categories. Despite these variations, our overall conclusion is that the increasing exposure of people and economic assets is the major cause of increasing trends in disaster impacts. This holds for long-term trends in economic losses as well as the number of people affected. We also found similar, though more qualitative, results for the number of people killed; in all three cases, the role played by climate change cannot be excluded. Furthermore, we found that trends in historic vulnerability tend to be stable over time, despite adaptation measures taken by countries. Based on these findings, we derived disaster impact projections for the coming decades. We argue that projections beyond 2030 are too uncertain, not only due to unknown changes in vulnerability, but also due to increasing non-stationarities in normalization relations.
MAG ID: 1982716423

Flood risk, vulnerability and environmental justice: Evidence and evaluation of inequality in a UK context - Walker, Gordon; Burningham, Kate (Critical Social Policy, 2011)
Flooding has only relatively recently been considered as an environmental justice issue. In this paper we focus on flooding as a distinct form of environmental risk and examine some of the key evidence and analysis that is needed to underpin an environmental justice framing of flood risk and flood impacts. We review and examine the UK situation and the body of existing research literature on flooding to fill out our understanding of the patterns of social inequality that exist in relation to both flood risk exposure and vulnerability to the diverse impacts of flooding. We then consider the various ways in which judgements might be made about the injustice or justice of these inequalities and the ways in which they are being sustained or responded to by current flood policy and practice. We conclude that there is both evidence of significant inequalities and grounds on which claims of injustice might be made, but that further work is needed to investigate each of these. The case for pursuing the framing of flooding as an environmental justice issue is also made.
MAG ID: 2099524802

Consultations sur les vulnérabilités psychosociales des inondations en contexte de changements climatiques - Annexe 1 - Projet CASSSIOPÉE - Turmel, J.; Lessard, L.; Lafond, A.; Robitaille, M-A (2022)

The Hazards of Mainstreaming: Climate change adaptation politics in three dimensions - Scoville-Simonds, Morgan; Jamali, Hameed; Hufty, Marc (World Development, 2020)

Weaponizing vulnerability to climate change - Thomas, Kimberley Anh; Warner, Benjamin P. (Global Environmental Change, 2019)

Analyser la vulnérabilité sociétale et territoriale aux inondations en milieu urbain dans le contexte des changements climatiques, en prenant comme cas d'étude la Ville de Montréal - Thomas, I.; Bleau, N. (2018)
28 Figure 7 : limites de la zone inondable et la zone inondée historiquement de la rive de Montréal de la rivière des prairies. [...] 68 Figure 27 : Aperçu de la table d’attributs de la base des données de la description de la sensibilité territoriale. [...] 41 Graphique 3 : Distribution des degrés de la sensibilité sociale par nombre d’aires de diffusion (206 AD au total) du secteur de la rivière des Prairies à Montréal à partir des résultats de l’indice ISSAIP des groupes de l’atelier de travail. [...] Cette analyse implique plusieurs étapes et le développement de plusieurs outils dont : la collecte des données disponibles et nécessaires pour réaliser un état des lieux des zones inondées historiquement pour une partie de la Ville de Montréal, la modélisation de l'espace occupé par l'eau selon différents niveaux d'eau possiblement atteints lors de débordement de la rivière, la collecte des donnée. [...] : la formation de réseaux de communication, la prise de décision, la création de consensus), qu’il est possible de mesurer, mais pas au moyen de données d’archives secondaires.
Keywords: Thomas_Isabelle

Impact of climate change on the vulnerability of drinking water intakes in a northern region - Leveque, B.; Burnet, J.-B.; Dorner, S.; Bichai, F. (Sustainable Cities and Society, 2021)
Keywords: Dorner_Sarah

Flood hazards, environmental rewards, and the social reproduction of risk - Oulahen, Greg (Geoforum, 2021)

Risk to Residential Property Values from Climate Change-Related Flooding Hazards: A Mixed Methods Approach - Nguyen, Quyen; Diaz-Rainey, Ivan; Moore, Tony; Thorsnes, Paul; Cox, Simon; McKenzie, Leigh; Stirk-Wang, Leon (SSRN Electronic Journal, 2019)
Keywords: Ouvrage_Collectif_Numéro1

Mapping Urban Risk: Flood Hazards, Race, & Environmental Justice In New York" - Maantay, Juliana A.; Maroko, Andrew R. (Applied Geography, 2009)
Abstract This paper demonstrates the importance of disaggregating population data aggregated by census tracts or other units, for more realistic population distribution/location. A newly developed mapping method, the Cadastral-based Expert Dasymetric System (CEDS), calculates population in hyper-heterogeneous urban areas better than traditional mapping techniques. A case study estimating population potentially impacted by flood hazard in New York City compares the impacted population determined by CEDS with that derived by centroid-containment method and filtered areal-weighting interpolation. Compared to CEDS, 37% and 72% fewer people are estimated to be at risk from floods city-wide, using conventional areal weighting of census data, and centroid-containment selection, respectively. Undercounting of impacted population could have serious implications for emergency management and disaster planning. Ethnic/racial populations are also spatially disaggregated to determine any environmental justice impacts with flood risk. Minorities are disproportionately undercounted using traditional methods. Underestimating more vulnerable sub-populations impairs preparedness and relief efforts.
MAG ID: 1965301779

What can be said about risks, vulnerabilities, and adaptation to climate change in Caribbean small island developing states (SIDS)? The case of Dominica. A qualitative study - Cooper, Sarah; Abraham, Christiana; Ravaliere, Terrilia; Harris-Glenville, Fiona; McPherson, Nickez; Cloos, Patrick (2023)
IntroductionCaribbean Small island developing states (SIDS) are generally qualified as disproportionately vulnerable to climate change, including extreme weather events like hurricanes. While many studies already documented the impacts of climate change on health in the wealthiest countries, there is little knowledge in this field in Caribbean SIDS. Our study aims to discuss health risks and vulnerabilities in a Caribbean context to inform future adaptation measures to climate change.MethodsOur paper is based on a qualitative study that was conducted in Dominica, a Caribbean SIDS. The data come from semi-structured interviews organized between March 2020 and January 2021 with people internally displaced following an extreme climate event, either tropical storm Erika (2015) or Hurricane Maria (2017), and with some people who migrated to Guadeloupe after Hurricane Maria. Interview guides were based on conceptual frameworks on climate change, migration and health, and vulnerability to climate change. Data were analyzed deductively based on frameworks and inductively to allow new codes to emerge.ResultsOur findings suggest that current knowledge of climate change by those who have been displaced by an extreme climate event varied greatly depending on the education level, class, and socioeconomic condition of the participant. Participants experienced various negative consequences from a storm or hurricane such as increased risk of relocation, lack of access to healthcare, and food, job, and water insecurities – all circumstances know to correlate with mental health issues. Participants suggested stronger dwellings, community preparedness committees to act sooner, and climate change sensitization and awareness campaigns to foster community unity and solidarity.ConclusionThese findings contribute to the perspectives and knowledge of climate change, highlighting that existing extreme climate event committees and government officials need to address structural and social barriers that can potentially increase social inequalities and lead to maladaptation to climate change with potential consequences on public health.
Keywords: Cloos_Patrick

Environmental vulnerability and resilience: Social differentiation in short‐ and long‐term flood impacts - Houston, Donald; Werritty, Alan; Ball, Tom; Black, Andrew (Transactions of the Institute of British Geographers, 2021)
This paper finds that social differentiation in flood impacts is relatively small soon after a flood, with some surprising results such as professionals and homeowners badly affected in the short‐term – but widens over time, with socially disadvantaged groups displaying less recovery. The paper concludes that vulnerability and resilience to flooding are sensitive to financial resources, institutional support (chiefly from a landlord), and capacity to deal with disruption (chiefly time availability, which is low among professionals and high among retired people). An implication of these findings is that existing indices of flood vulnerability that use multiple measures of social deprivation should be used with caution, as not all conventional aspects of social deprivation are necessarily associated with greater vulnerability to flood impacts. , This paper reports household questionnaire survey results on vulnerability and resilience to flooding from one of the largest and most representative samples ( n = 593) of households up to 12 years after they were flooded, and is one of the first to provide detailed analysis of social differentiation in long‐term flood impacts. A novel finding is that social differentiation in flood impacts is relatively small soon after a flood, but widens over time, with socially disadvantaged groups displaying less recovery. The patterns of social differentiation in vulnerability and resilience to flooding differ markedly according to the type and timescale of the impact, with some normally socially advantaged groups (e.g., professionals and homeowners) being most vulnerable to short‐term impacts. Consistent with some existing studies, we found that older residents (age 70+) have greater resilience to flood impacts, although our sample may not capture the frailest individuals. As in previous research, low income is linked to lower resilience, particularly in the long term. We find that prior experience of flooding, despite enhancing preparedness, overall erodes rather than enhances resilience to flooding. Flood warnings are effective at reducing vulnerability to short‐term impacts. Underlying influences on resilience to natural disasters are complex and may only be revealed by multivariate analysis and not always be evident in simple observed patterns. The paper concludes that vulnerability and resilience to flooding are sensitive to financial resources, institutional support (chiefly from a landlord), and capacity to deal with disruption (chiefly time availability, which is low among professionals and high among retired people). An implication of these findings is that existing indices of flood vulnerability that use multiple measures of social deprivation should be used with caution, as not all conventional aspects of social deprivation are necessarily associated with greater vulnerability to flood impacts.

Future Changes in Flood Hazards across Canada under a Changing Climate - Gaur, Ayushi; Gaur, Abhishek; Simonovic, Slobodan P. (Water, 2018)
Climate change has induced considerable changes in the dynamics of key hydro-climatic variables across Canada, including floods. In this study, runoff projections made by 21 General Climate Models (GCMs) under four Representative Concentration Pathways (RCPs) are used to generate 25 km resolution streamflow estimates across Canada for historical (1961–2005) and future (2061–2100) time-periods. These estimates are used to calculate future projected changes in flood magnitudes and timings across Canada. Results obtained indicate that flood frequencies in the northernmost regions of Canada, and south-western Ontario can be expected to increase in the future. As an example, the historical 100-year return period events in these regions are expected to become 10–60 year return period events. On the other hand, northern prairies and north-central Ontario can be expected to experience decreases in flooding frequencies in future. The historical 100-year return period flood events in these regions are expected to become 160–200 year return period events in future. Furthermore, prairies, parts of Quebec, Ontario, Nunavut, and Yukon territories can be expected to experience earlier snowmelt-driven floods in the future. The results from this study will help decision-makers to effectively manage and design municipal and civil infrastructure in Canada under a changing climate.
MAG ID: 2896881190

Social Vulnerability to Environmental Hazards - Cutter, Susan L.; Boruff, Bryan; Shirley, W. Lynn (Social Science Quarterly, 2003)
County-level socioeconomic and demographic data were used to construct an index of social vulnerability to environmental hazards, called the Social Vulnerability Index (SoVI) for the United States based on 1990 data. Copyright (c) 2003 by the Southwestern Social Science Association.
MAG ID: 2031553845

Exploring spatial heterogeneity and environmental injustices in exposure to flood hazards using geographically weighted regression - Chakraborty, Liton; Rus, Horatiu; Henstra, Daniel; Thistlethwaite, Jason; Minano, Andrea; Scott, Daniel (Environmental Research, 2022)

A place-based socioeconomic status index: Measuring social vulnerability to flood hazards in the context of environmental justice - Chakraborty, Liton; Rus, Horatiu; Henstra, Daniel; Thistlethwaite, Jason; Scott, Daniel (International Journal of Disaster Risk Reduction, 2020)
Keywords: Ouvrage_Collectif_Numéro1